Battery thermal management member

By using a thermal management component composed of an aerogel composition in the lithium-ion battery module, the problems of battery thermal management and flame spread are solved, and efficient thermal insulation and flame blocking are achieved, which are suitable for space-constrained battery systems.

CN119872008APending Publication Date: 2025-04-25ASPEN AEROGELS INC
View PDF 39 Cites 0 Cited by

Patent Information

Application Number
CN202510084666.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-11-30
Filing Date
2021-01-07
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively manage thermal and flame spread of lithium-ion batteries, especially in space-constrained battery modules, and conventional insulating materials do not perform well at high temperatures.

Method used

Using a high-performance battery thermal management member including an aerogel composition, an excellent thermal insulation and flame blocking effect is achieved by providing a heat-proof layer and an elastic layer between the battery cells by utilizing the low density and high porosity characteristics of the aerogel.

Benefits of technology

Effective resistance to heat spread and flame spread is achieved, reducing the thickness and weight of the materials used, while maintaining good compression, compression elasticity and compliance properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119872008A_ABST
    Figure CN119872008A_ABST
Patent Text Reader

Abstract

Battery thermal management members, particularly battery thermal management materials, compositions, and systems are provided. Exemplary embodiments include a battery thermal management member. The battery thermal management member may include a heat shielding layer and an elastic layer. Methods of making or producing such battery thermal management members are also provided. In certain embodiments, the thermal protection layer may include mica, microporous silica, ceramic fibers, mineral wool, aerogel, or a combination thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention is a divisional application of a PCT patent application entered into China with Chinese patent application number 2021800194429, invention name “Battery Thermal Management Component” and international application date January 17, 2021.

[0002] Citations of Related Applications

[0003] This application claims the benefit of priority to U.S. Provisional Patent Application No. 62 / 958,135 filed on January 7, 2020, U.S. Provisional Patent Application No. 63 / 056,527 filed on July 24, 2020, U.S. Patent Application Serial No. 17 / 106,940 filed on November 30, 2020, and U.S. Patent Application Serial No. 17 / 106,763 filed on November 30, 2020, each of which is incorporated herein by reference in its entirety, with any definitions of terms in this application controlling. Technical Field

[0004] The present invention generally relates to battery thermal management. More specifically, the present disclosure relates to compositions and systems for battery thermal management. In specific embodiments, the present disclosure relates to high-performance battery thermal management compositions and systems including aerogel technology for separating battery cells or insulating battery components. Background Art

[0005] Low-density aerogel materials are widely considered to be the best solid insulators available. Aerogels act as insulators primarily by minimizing conduction (low structural density results in a tortuous path for energy transfer through the solid framework), convection (large pore volume and extremely small pore size result in minimized convection), and radiation (using IR absorbing or scattering dopants). Aerogels can be used in a wide range of applications, including thermal and cold insulation, sound insulation, electronic dielectrics, aviation, energy storage and production, and filtration. In addition, aerogel materials exhibit a variety of other interesting acoustic, optical, mechanical and chemical properties, which make them widely used in a variety of insulating and non-insulating applications.

[0006] Thermal insulation suitable for reliably controlling heat flow from heat-generating components in small spaces and providing safety and flame spread prevention to these products is needed in the fields of electronics, industrial and automotive technology. Thermal insulation sheets with excellent properties when compressed can be used to address these needs, for example, as separators for lithium-ion battery modules.

[0007] Safety standards for lithium-ion batteries include flame exposure testing. The flame exposure test is a test method that subjects a battery cell in a battery module to thermal runaway and then determines whether a fire or rupture occurs due to heat spread to other battery cells, including adjacent battery cells. Safety designs intended to block thermal runaway from spreading to adjacent battery cells typically include materials with excellent thermal insulation properties between battery cells.

[0008] Conventional types of insulating materials, such as foams or fiber sheets, can withstand high temperatures but have relatively low insulating or heat-retaining capabilities. For these materials, the thickness of the insulating material must be increased to provide effective thermal management. However, the space requirements of the battery module limit the size of the module and the space between the battery cells within the module. Other refractory materials, such as mica or ceramic sheets, can withstand high temperatures but are relatively incompressible and also have low insulating capabilities. These materials may not be suitable for battery systems in which the battery cells expand and contract during operation, such as soft-pack batteries and square batteries. Similarly, it is desirable to limit the total weight of the battery module. Therefore, it is necessary to achieve resistance to heat spread and flame spread while minimizing the thickness and weight of the material used to provide the necessary thermal properties while providing the desired mechanical properties for a given battery system. Different types of insulation systems, materials, and methods are needed to provide effective insulation, heat preservation, and flame spread prevention.

[0009] Aerogel materials are known to have thermal resistance values ​​that are about 2 to 6 times greater than other common types of insulating materials (e.g., foam, fiberglass, etc.). Aerogels can improve effective shielding and thermal insulation without significantly increasing the thickness of the insulating material or adding extra weight. Aerogels are known to be a class of structures with low density, open cell structure, large surface area, and nanoscale pore size.

[0010] U.S. Patent Publication No. 2012 / 0142802 of Steinke discloses an open-cell foam filled with aerogel particles. U.S. Patent Publication No. 2019 / 0161909 of Oikawa discloses a thermal insulation sheet comprising a nonwoven fabric and an aerogel. However, these documents do not disclose materials having the desired thermal, fire, mechanical and hydrophobic properties and a combination of multiple desired properties for use in a battery thermal management member, or methods for producing these materials.

[0011] It would be desirable to provide battery thermal management components and systems with improved performance in various aspects, including compressibility, compression elasticity, compliance, heat resistance, hydrophobicity, fire reaction, etc., both individually and in one or more combinations. With reference to the state of the art as a whole at the time of the completion of this invention, it would not be obvious to one of ordinary skill in the art of the present invention how the shortcomings of the prior art can be overcome.

[0012] Although certain aspects of conventional technology have been discussed to facilitate the disclosure of the present invention, applicants by no means deny these aspects of technology, and it is contemplated that the claimed invention may encompass one or more of the conventional technology aspects discussed herein.

[0013] The present invention can solve one or more problems and deficiencies in the prior art. However, it is contemplated that the present invention may prove useful in solving other problems and deficiencies in some technical fields. Therefore, the claimed invention should not necessarily be considered to be limited to solving any specific problem or defect discussed herein.

[0014] In this specification, when known documents, acts or items are referred to or discussed, such reference or discussion is not an admission that the known documents, acts or items, or any combination thereof, were publicly available, part of the common general knowledge known to the public on the priority date, or otherwise constitute prior art under applicable legal provisions; or are known to be relevant to attempts to solve any problem addressed in this specification. Summary of the invention

[0015] The long-standing but heretofore unfulfilled need for improved aerogel compositions has now been satisfied by a new, useful and non-obvious invention.

[0016] In general aspects, the present disclosure provides battery thermal management components and systems that are durable and easy to handle, have good resistance to heat spread and flame spread while minimizing the thickness and weight of the materials used, and also have good compressibility, compression elasticity, and compliance properties.

[0017] In an exemplary aspect, the present disclosure provides a battery thermal management component, which includes a heat protection layer and a resilient layer, for example, the resilient layer includes one or more organic materials. In an exemplary embodiment, the heat protection layer has a thermal conductivity of less than about 65mW / mK, for example, the heat protection layer can at least maintain the surface of the resilient layer below the decomposition temperature of at least one of the organic materials.

[0018] In some embodiments, the heat protection layer is arranged adjacent to the elastic layer. In some embodiments, the heat protection layer is arranged to contact with at least one elastic layer. In some embodiments, the battery thermal management component includes a second heat protection layer. In these embodiments, the first heat protection layer and the second heat protection layer may be arranged on opposite sides of at least one elastic layer. For example, at least one of the first heat protection layer and the second heat protection layer may be arranged to contact with at least one elastic layer.

[0019] In any of the above embodiments, the elastic layer may include a compressible material. In some embodiments, the chemical decomposition temperature of the compressible material is greater than about 200°C. In some embodiments, the chemical decomposition temperature of the compressible material is greater than about 240°C. In some embodiments, the chemical decomposition temperature of the compressible material is greater than about 280°C. In some embodiments, the chemical decomposition temperature of the compressible material is in the range of about 200°C to about 300°C. In some embodiments, the chemical decomposition temperature of the compressible material is greater than about 300°C. In some embodiments, the chemical decomposition temperature of the compressible material is greater than about 350°C. In some embodiments, the chemical decomposition temperature of the compressible material is in the range of about 300°C to about 400°C.

[0020] In an exemplary embodiment, the compressible material includes a material selected from the group consisting of: siloxane, polyolefin, polyurethane, phenolics, melamine, cellulose acetate, and polystyrene. In an exemplary embodiment, the heat shielding layer includes a material selected from the group consisting of mica, microporous silica, ceramic fiber, mineral wool, and combinations thereof. For example, at least one of the first and second heat shielding layers may include a material selected from the group consisting of mica, microporous silica, ceramic fiber, mineral wool, and combinations thereof. For another example, both the first and second heat shielding layers may include a material selected from the group consisting of mica, microporous silica, ceramic fiber, mineral wool, and combinations thereof.

[0021] In some embodiments, the heat protection layer includes an aerogel composition. For example, at least one of the first and second heat protection layers may include an aerogel composition. For another example, both the first and second heat protection layers may include an aerogel composition. The aerogel of the aerogel composition may include inorganic, organic or inorganic / organic hybrid materials (hybrid material). In an exemplary embodiment, the aerogel composition is a silica aerogel composition. The aerogel composition may include a reinforcing material. For example, the reinforcing material is present in the aerogel composition. In some embodiments, the reinforcing material comprises fibers. For example, the fibers may be selected from the group consisting of discrete fibers, textile materials, non-woven materials, needled nonwovens, cotton wool, webs, pads, felts, and combinations thereof.

[0022] In another general aspect, the present disclosure provides an aerogel composition, for example, a reinforced aerogel composition, which is durable and easy to handle, has good resistance to heat spread and flame spread, while minimizing the thickness and weight of the material used, and also has good compressibility, compression elasticity and compliance properties. In another general aspect, the present disclosure provides a thermal control member or a battery thermal management member, which includes an aerogel composition, a reinforced aerogel composition, or a combination thereof. For example, a thermal control member or a battery thermal management member according to aspects disclosed herein may include at least one layer of an aerogel composition or a reinforced aerogel composition. For another example, a thermal control member or a battery thermal management member according to aspects disclosed herein may include multiple layers of aerogel composition or a reinforced aerogel composition.

[0023] In an exemplary aspect, the present disclosure provides a thermal control member or a battery thermal management member comprising an aerogel composition. In certain embodiments, the thermal control member or the battery thermal management member is substantially planar and has a first major outer surface (first major outer surface) and a second major outer surface. In an exemplary embodiment, the aerogel composition includes one or more additives. In some embodiments, the additive may be present at a level of about 5% to 20% by weight of the aerogel composition. In some embodiments, the additive may be present at a level of about 10% to 20% by weight of the aerogel composition. In certain embodiments, the thermal control member or the battery thermal management member has a thermal conductivity of less than about 40mW / mK. In an exemplary embodiment, the thermal control member or the battery thermal management member comprises a multilayer aerogel composition.

[0024] In another exemplary aspect, the present disclosure provides a thermal control member or a battery thermal management member, which includes at least one layer of an aerogel composition, at least one compliant member and a thermally capacitive material. The aerogel composition includes one or more additives, the additives being present at a level of at least about 5% to 20% by weight of the aerogel composition. In some embodiments, the additives may be present at a level of about 10% to 20% by weight of the aerogel composition. In an exemplary embodiment, the thermal control member or the battery thermal management member includes multiple layers of aerogel composition. In some embodiments, the thermally capacitive material is arranged between at least two layers of aerogel composition. The thermally capacitive material may be any material having a specific heat capacity of at least about 0.3 J / (gC). In some embodiments, the material providing thermal capacity has a specific heat capacity of at least about 0.5 J / (gC). For example, the thermally capacitive material may include at least one layer comprising a metal. In an exemplary embodiment, at least one compliant member may include a compressible material, i.e., a material that can be compressed to reduce its thickness while providing the desired compressive strength. For example, the compliant member may include a material selected from the group consisting of polyolefins, polyurethanes, phenolic resins, melamine, cellulose acetate, and polystyrene. The compliant member may be disposed adjacent to the aerogel composition or the thermally capacitive material. In an exemplary embodiment, the compliant member is located between at least two layers of aerogel composition. In some embodiments, the compliant member is disposed between both the aerogel composition layer and the thermally capacitive material layer.

[0025] In some embodiments, the thermal control member or battery thermal management member has a thermal conductivity of less than about 30mW / mK or less, less than about 25mW / mK, less than about 20mW / mK, less than about 18mW / mK, less than about 16mW / mK, less than about 14mW / mK, less than about 12mW / mK, less than about 10mW / mK, less than about 5mW / mK, or a thermal conductivity within a range between any combination of the above thermal conductivities. In an exemplary embodiment, one or more additives include a fire-class additive. In an exemplary embodiment, one or more additives include a sunscreen. In some embodiments, one or more additives include a combination of a fire-class additive and a sunscreen. For example, one or more additives may include a clay mineral, such as kaolin. For another example, one or more additives can be selected from the group consisting of boron carbide, diatomaceous earth, manganese ferrite, MnO, NiO, SnO, Ag2O, Bi2O3, carbon black, graphite, titanium oxide (titanium oxide), iron titanium oxide (iron titanium oxide), aluminum oxide (aluminum oxide), zirconium silicate, zirconium oxide (zirconium oxide), iron (II) oxide (iron (II) oxide), iron (III) oxide (iron (III) oxide), manganese dioxide, iron titanium oxide (ilmenite), chromium oxide (chromium oxide), silicon carbide, titanium carbide, tungsten carbide or mixtures thereof. In a preferred embodiment, the one or more additives include silicon carbide.

[0026] In an exemplary embodiment, when the first major outer surface is exposed to a temperature of 650°C or more, the thermal control member or battery thermal management member maintains a temperature of 120°C or less at the second major surface for at least about 1 minute. In some embodiments, when the first major outer surface is exposed to a temperature of 650°C or more, the thermal control member or battery thermal management member maintains a temperature of 75°C or less at the second major outer surface for at least about 30 seconds. In some embodiments, when the first major outer surface is exposed to a temperature of 650°C or more, the thermal control member or battery thermal management member maintains a temperature of 150°C or less at the second major outer surface for at least about 90 seconds. In some embodiments, when the first major outer surface is exposed to a temperature of 650°C or more, the thermal control member or battery thermal management member maintains a temperature of 150°C or less at the second major outer surface for at least about 90 seconds. In some embodiments, when the first major outer surface is exposed to a temperature of 650°C or more, the thermal control member or battery thermal management member maintains a temperature of 170°C or less at the second major outer surface for at least about 90 seconds. In some embodiments, the thermal control member or battery thermal management member maintains a temperature of 180°C or less at the second major outer surface for at least about 2 minutes, and preferably at least about 4 minutes, when the first major outer surface is exposed to a temperature of 650°C or greater.

[0027] In another embodiment, these thermal profiles are achieved when the thermal control component or battery thermal management component is integrated into an electric vehicle system along with other components having a variety of configurations and environments. For example, the thermal control component or battery thermal management component may be integrated into a system where the thermal control component or battery thermal management component and other components may be subject to ambient pressures, temperatures, and compressions (including from gases other than air), such as a battery system.

[0028] In an exemplary embodiment, the aerogel composition has an uncompressed thickness in a range of about 1 mm to about 10 mm. For example, the aerogel composition can have an uncompressed thickness in a range of about 1 mm to about 5 mm. For another example, the aerogel composition can have an uncompressed thickness of about 2 mm, an uncompressed thickness of about 3 mm, or an uncompressed thickness of about 4 mm.

[0029] In certain embodiments, the aerogel composition has a thickness of about 0.60 g / cm 3 Or lower, about 0.50g / cm 3 Or lower, about 0.40g / cm 3 Or lower, about 0.30g / cm 3 Or lower, about 0.25g / cm 3 Or lower, about 0.20g / cm 3 Or lower, about 0.18g / cm 3 Or lower, about 0.16g / cm 3Or lower, about 0.14g / cm 3 Or lower, about 0.12g / cm 3 Or lower, about 0.10g / cm 3 Or lower, about 0.05g / cm 3 Or lower, about 0.01g / cm 3 or less, or a density in a range between any two of these values. In an exemplary embodiment, the aerogel composition has a density of less than about 0.3 g / cm 3 density.

[0030] In an exemplary aspect, the present disclosure provides a battery module including a first battery cell, a second battery cell, and a thermal control member or a battery thermal management member according to embodiments disclosed herein disposed between at least the first battery cell and the second battery cell.

[0031] In an exemplary aspect, the present disclosure provides a battery module or battery pack, which includes at least one battery cell and a thermal control member or battery thermal management member according to an embodiment disclosed herein arranged on the battery cell or battery module, for example, on the surface of at least one battery cell or on the surface of the battery module. For example, the battery module or battery pack has an inner surface and an outer surface. In some embodiments, the thermal control member or battery thermal management member is located on the inner surface of the battery module or battery pack. In some embodiments, the thermal control member or battery thermal management member is located on the outer surface of the battery module or battery pack.

[0032] In an exemplary embodiment, the thermal control member or battery thermal management member includes an aerogel composition.In some embodiments, the thermal control member or battery thermal management member has an energy absorption capacity in a range of about 25 J / g to about 225 J / g.

[0033] In embodiments of aspects disclosed herein, the aerogel composition may include a reinforcing material. For example, the reinforcing material includes fibers. For example, the reinforcing material may be selected from the group consisting of discrete fibers, textile materials, non-textile materials, needle-shaped non-textile fabrics, cotton wool, mesh, pads, felts, and combinations thereof. In some embodiments, the reinforcing material includes an open-cell macroporous framework ("OCMF") material. For example, an OCMF material may include a melamine-based foam or a urethane-based polymer foam. In other embodiments, the reinforcing material may include a combination of fibers and OCMF materials.

[0034] In embodiments of aspects disclosed herein, the thermal control member or battery thermal management member may have an uncompressed thickness in the range of about 2 mm to about 10 mm. For example, the thermal control member or battery thermal management member may have an uncompressed thickness of about 2 mm, about 3 mm, about 4 mm, about 5 mm, about 6 mm, about 7 mm, about 8 mm, about 9 mm, about 10 mm, or a range between any of the above thicknesses. In an exemplary embodiment, the thermal control member or battery thermal management member may have an uncompressed thickness in the range of about 2 mm to about 7 mm.

[0035] In some embodiments of the aspects disclosed herein, the thermal control member or the battery thermal management member may further include an encapsulation member that forms at least one of the first or second outer surfaces. For example, the aerogel composition may include the encapsulation member. For example, the encapsulation member may include an encapsulation layer or coating surrounding the aerogel composition and / or the thermal control member or the battery thermal management member. The encapsulation member may include at least one vent to allow air to flow into and out of the panel, and in some embodiments, may include a particulate filter to retain particulate matter within the encapsulation member.

[0036] In an exemplary embodiment, the aerogel composition of the thermal control component or battery thermal management component is hydrophobic. For example, the aerogel composition has a liquid water absorption of less than about 15 wt%.

[0037] In an exemplary embodiment, the aerogel of the aerogel composition comprises an inorganic, organic, or inorganic / organic hybrid material. For example, the aerogel composition is a silica aerogel composition. In certain embodiments, the aerogel composition comprises alkylated silica.

[0038] In certain embodiments, the aerogel composition is lofty. For the purposes of this patent, a lofty aerogel composition is defined as an aerogel composition that exhibits volume and some elasticity (with or without full volume recovery) properties. In certain embodiments, a lofty aerogel composition is (i) compressible to at least 50%, preferably at least 65%, and most preferably at least 80% of its original or uncompressed thickness, and (ii) sufficiently elastic so that after being compressed for a few seconds it will recover to at least 70%, preferably at least 75%, and most preferably at least 80% of its original or uncompressed thickness.

[0039] In some embodiments, the reinforcement material may include a reinforcement body, which includes multiple layers of material. For example, the multiple layers of material may be bonded together. In an exemplary embodiment, at least one of the multiple layers may include a first material and at least one other of the multiple layers may include a second material. The first material and the second material may have the same or different material properties. For example, the first material may be more compressible than the second material. For another example, the first material may include a closed cell and the second material may include an open cell.

[0040] In some embodiments of the aspects disclosed herein, the thermal control member or battery thermal management member may include multiple layers. For example, the thermal control member or battery thermal management member may include at least one layer of thermally conductive material or at least one layer including a thermally conductive material, for example, a layer including a metal, carbon, a thermally conductive polymer, or a combination thereof. As used in the context of these embodiments, a thermally conductive material refers to a material having a thermal conductivity greater than that of an aerogel composition. In certain embodiments, the thermally conductive material has a thermal conductivity at least about one order of magnitude greater than that of an aerogel composition. In some embodiments, the thermal control member or battery thermal management member may include multiple layers of aerogel composition. In certain embodiments, the thermal control member or battery thermal management member may include at least one layer of thermally conductive material disposed adjacent to the aerogel composition. In certain embodiments, the thermal control member or battery thermal management member may include at least one layer of thermally conductive material disposed between at least two layers in the multilayer aerogel composition. In some embodiments, the thermal control member or battery thermal management member may include particles of thermally conductive material disposed within a layer of the thermal control member or battery thermal management member, for example, within a layer of an aerogel composition.

[0041] In an exemplary embodiment, the thermal control member or battery thermal management member may include a material or material layer (i.e., a thermal capacitance material) that provides thermal capacity, for example, a material with a specific heat capacity of at least about 0.3 J / (gC). In some embodiments, the material that provides thermal capacity has a specific heat capacity of at least about 0.5 J / (gC). For example, the material that provides thermal capacity may include a metal such as aluminum, titanium, nickel, steel, iron, or a combination thereof. In some embodiments, the thermal control member or battery thermal management member may include a material layer or coating that provides thermal capacity. In some embodiments, the thermal control member or battery thermal management member may include particles of a material that provides thermal capacity arranged in a layer of the thermal control member or battery thermal management member, for example, a layer of an aerogel composition. In certain embodiments, the thermal control member or battery thermal management member may include at least one layer of a material that provides thermal capacity disposed adjacent to the aerogel composition. In certain embodiments, the thermal control member or battery thermal management member may include at least one layer of a material that provides thermal capacity disposed between at least two layers in a multilayer aerogel composition. In an exemplary embodiment, the thermal control member or battery thermal management member may include both thermally conductive and thermally capacitive materials. For example, the thermal control member or battery thermal management member may include a material that provides both thermal capacity and thermal conductivity, for example, a metal such as aluminum, titanium, nickel, steel, iron, or a combination thereof. For another example, the thermal control member or battery thermal management member may include one or more different materials or material layers that provide thermal capacity, thermal conductivity, or a combination thereof, respectively, for example, a layer including a metal and a layer including a thermally conductive polymer.

[0042] In some embodiments, a thermally conductive paste may be used between layers of a thermal control component or a battery thermal management component to ensure uniform and consistent thermal conductivity between these layers. As used herein, thermally conductive paste refers to a variety of materials also known as thermally conductive compounds, thermal grease, thermal interface material (TIM), thermally conductive gel, heat sink, heat sink compound, and heat sink paste. For example, a layer of thermally conductive paste may be disposed between an aerogel composition and other layers, such as one or more layers including a thermally conductive or thermally capacitive material.

[0043] In embodiments of aspects disclosed herein, the composition may further include at least one facing layer, as discussed in more detail below. For example, the facing layer may be a layer selected from the group consisting of a polymer sheet, a metal sheet, a fiber sheet, and a fabric sheet. In an exemplary embodiment, the facing layer may include a thermally conductive material, a material providing heat capacity, or a combination thereof. In some embodiments, the facing layer may be connected to the composition, for example, by an adhesive mechanism selected from the following: an aerosol adhesive, a urethane-based adhesive, an acrylate adhesive, a hot melt adhesive, an epoxy resin, a rubber resin adhesive, a polyurethane composite adhesive, and a combination thereof. In some embodiments, the facing layer may be connected to the composition by a non-adhesive mechanism, for example, a mechanism selected from the group consisting of the following: flame gluing, stitching, a sealed bag, a rivet, a button, a clamp, a coating, a bracket, and a combination thereof. In some embodiments, the facing layer may be connected to the composition using a combination of any of the above-mentioned adhesive and non-adhesive mechanisms. In some embodiments of the above-mentioned aspects, the thermal control member or the battery thermal management member may further include at least one layer of conductive material or heat-capacitive material. For example, at least one layer of conductive or heat-capacitive material may include a metal, carbon, a conductive polymer, or a combination thereof. In some examples, the at least one layer of conductive material comprising carbon can be a highly oriented graphite material, such as a pyrolytic graphite sheet or similar material.

[0044] In embodiments of aspects disclosed herein, one or more additives are selected from the group consisting of boron carbide, diatomaceous earth, manganese ferrite, MnO, NiO, SnO, Ag2O, Bi2O3, carbon black, graphite, titanium oxide, iron titanium oxide, aluminum oxide, zirconium silicate, zirconium oxide, iron (II) oxide, iron (III) oxide, manganese dioxide, iron titanium oxide (ilmenite), chromium oxide, silicon carbide, titanium carbide, tungsten carbide, or mixtures thereof. In certain embodiments, the one or more additives may include silicon carbide. In specific embodiments, the one or more additives do not include whiskers or fibers of silicon carbide.

[0045] In some embodiments, the aerogel composition further comprises one or more other additives. For example, one or more other additives comprise a fire-type additive. In these or other embodiments of the above aspects, the composition is low-flammable, non-flammable, low-burning or non-burning. In some embodiments, the additive comprises a clay mineral, for example, kaolin. In these or other embodiments, the one or more additives comprise a combination of a fire-type additive and a sunscreen.

[0046] In addition, the aerogel materials or frameworks of various embodiments of the present disclosure are practiced using aerogel particle-based slurries or suspensions infiltrated into the reinforcing materials described in various embodiments. Various embodiments of the present disclosure can be practiced using non-particulate aerogel materials produced in situ by infiltrating reinforcing materials with various gel precursors in a suitable solvent and then removing the solvent using various methods, including the use of supercritical fluids, or at elevated temperatures and ambient pressures or at subcritical pressures.

[0047] In separate embodiments, the present disclosure includes thermal control components or battery thermal management components comprising an aerogel composition, for example, an OCMF-reinforced or fiber-reinforced aerogel composition, comprising one or more or even all of the above-described properties and characteristics, including various combinations and methods of making the same.

[0048] Embodiments of the thermal barriers and aerogel compositions disclosed herein are useful for separation, insulation and protection of battery cells or battery assemblies having batteries of any configuration, for example, pouch cells, cylindrical cells, prismatic cells, and battery packs and modules incorporating or including any of these cells. The thermal barriers and aerogel compositions disclosed herein are useful in lithium-ion batteries, solid batteries, and any other energy storage device or technology where separation, insulation and protection are necessary.

[0049] These and other important objects, advantages and features of the present invention will become clear as the disclosure proceeds.

[0050] The present invention accordingly comprises the features of construction, combination of elements and arrangement of parts which will be exemplified in the disclosure set forth hereinafter and the scope of the invention will be indicated in the claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 is a diagram showing a thermal control component or battery thermal management component controlling time and temperature behavior according to certain embodiments disclosed herein;

[0052] Figure 2 is a diagram showing a thermal control component or battery thermal management component controlling time and temperature behavior according to certain embodiments disclosed herein;

[0053] Figure 3 is a graph showing the relationship between stress and strain of a thermal control component or a battery thermal management component according to certain embodiments disclosed herein;

[0054] Figure 4 is a diagram showing a thermal control component or battery thermal management component controlling time and temperature behavior according to certain embodiments disclosed herein;

[0055] Figure 5 is an exemplary thermal control component or battery thermal management component according to certain embodiments disclosed herein;

[0056] Figure 6 Schematically shows a thermal control component or a battery thermal management component according to certain embodiments disclosed herein;

[0057] Figure 7 Schematically shows a thermal control component or a battery thermal management component according to certain embodiments disclosed herein;

[0058] Figure 7 Schematically shows a thermal control component or a battery thermal management component according to certain embodiments disclosed herein;

[0059] Figure 8 Schematically shows a thermal control component or a battery thermal management component according to certain embodiments disclosed herein;

[0060] Fig. 9 Schematically shows a thermal control component or a battery thermal management component according to certain embodiments disclosed herein;

[0061] Fig.10 A thermal control component or battery thermal management component according to certain embodiments disclosed herein is schematically shown.

[0062] Fig.11 A thermal control component or battery thermal management component according to certain embodiments disclosed herein is schematically shown. DETAILED DESCRIPTION

[0063] In the following detailed description of the preferred embodiment, reference is made to the accompanying drawings, which form a part thereof and in which are shown by way of illustration specific embodiments in which the invention may be practiced. It is understood that other embodiments may be used and structural changes may be made without departing from the scope of the invention.

[0064] As used in this specification and the appended claims, the singular forms of "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. As used in this specification and the appended claims, the term "or" is generally used in its sense including "and / or" unless the context clearly dictates otherwise.

[0065] As used herein, "about" means approximately or close to, and in the context of a described numerical value or range, means ±5% of a numerical value. In one embodiment, the term "about" may include conventional rounding according to numerical significant figures. In addition, the phrase "about 'X' to 'Y'" includes "about 'X' to about 'Y'".

[0066] As used herein, the terms "composition" and "composite material" are used interchangeably.

[0067] Aerogels are a class of porous materials with open cells that comprise an interconnected structural framework with a corresponding pore network integrated within the framework and an interstitial phase within the pore network consisting primarily of a gas, such as air. Aerogels are generally characterized by low density, high porosity, large surface area, and small pore size. Aerogels can be distinguished from other porous materials by their physical and structural properties.

[0068] In the context of the present disclosure, the term "aerogel" or "aerogel material" refers to a gel comprising a framework of interconnected structures having a corresponding interconnected network of pores integrated within the framework and containing a gas, such as air, as a dispersed interstitial medium; and characterized by the following physical and structural properties attributable to the aerogel (as measured by nitrogen porosity): (a) an average pore size in the range of about 2 nm to about 100 nm, (b) a porosity of at least 80% or greater, and (c) a porosity of about 100 nm. 2 / g or greater surface area.

[0069] Aerogel materials of the present disclosure therefore include any aerogel or other open cell material that meets the defining elements described in the preceding paragraphs; including materials that may otherwise be classified as xerogels, cryogels, ambigels, microporous materials, and the like.

[0070] The aerogel material may also be further characterized by other physical properties, including: (d) a pore volume of about 2.0 mL / g or greater, specifically about 3.0 mL / g or greater; (e) a density of about 0.50 g / cc or less, specifically about 0.3 g / cc or less, more specifically about 0.25 g / cc or less; and (f) at least 50% of the total pore volume comprises pores having a pore size between 2 and 50 nm (although embodiments disclosed herein include aerogel frameworks and compositions containing pores having a pore size greater than 50 nm, as discussed in more detail below). However, these other properties need not be met for characterization of a compound as an aerogel material.

[0071] In the context of the present disclosure, the term "innovative processing and extraction techniques" refers to methods of replacing the liquid interstitial phase in a wet gel material with a gas, such as air, in such a way that the method results in low pore collapse and low shrinkage of the gel framework structure. Drying techniques, such as ambient pressure evaporation, typically introduce strong capillary pressures and other mass transfer limitations at the liquid-gas interface of the interstitial phase to be evaporated or removed. The strong capillary forces generated by liquid evaporation or removal can cause significant pore shrinkage and framework collapse within the gel material. During liquid interstitial phase extraction, the use of innovative processing and extraction techniques reduces the adverse effects of capillary forces on the pores and framework of the gel during liquid extraction (also known as solvent removal or drying).

[0072] In certain embodiments, innovative processing and extraction techniques use near critical or supercritical fluids, or near critical or supercritical conditions, to extract liquid interstitial phases from wet gel materials. This can be achieved by removing the liquid interstitial phase from the gel near or above the critical point of the liquid or liquid mixture. Co-solvents and solvent exchange can be used to optimize near critical or supercritical fluid extraction methods.

[0073] In certain embodiments, innovative processing and extraction techniques include modification of the gel framework to reduce the irreversible effects of capillary pressure and other mass transfer limitations at the liquid-gas interface. This embodiment may include treating the gel framework with a hydrophobic agent or other functionalizing agent that enables the gel framework to withstand or recover from any collapse forces during liquid extraction below the critical point of the liquid gap phase. This embodiment may also include the incorporation of functional groups or framework elements that provide a sufficiently high framework modulus to withstand or recover from collapse forces during liquid extraction below the critical point of the liquid gap phase.

[0074] In the context of the present disclosure, the term "framework" or "framework structure" refers to a network of interconnected oligomers, polymers or particles that form a solid structure of a material. In the context of the present disclosure, the term "aerogel framework" or "aerogel framework structure" refers to a network of interconnected oligomers, polymers or colloidal particles that form a solid structure of a gel or aerogel. The polymers or particles that make up the aerogel framework structure typically have a diameter of about 100 angstroms. However, the framework structure of the present disclosure may also include a network of interconnected oligomers, polymers or colloidal particles of all diameter sizes that form a solid structure within a material such as a gel or aerogel. In addition, the term "silica-based aerogel" or "silica-based aerogel framework" refers to an aerogel framework in which silica accounts for at least 50% of the oligomers, polymers or colloidal particles (by weight) that form a solid framework structure within the gel or aerogel.

[0075] In the context of the present disclosure, the term "aerogel composition" refers to any composite material that includes an aerogel material as a component of the composite material. Examples of aerogel compositions include, but are not limited to, fiber-reinforced aerogel composites; aerogel composites that include additive elements, such as sunscreens; aerogel composites that are reinforced by an open-cell macroporous framework; aerogel-polymer composites; and composites in which aerogel particles, particles, granules, beads or powders are incorporated into solid or semi-solid materials, such as in combination with binders, resins, cements, foams, polymers or similar solid materials. Aerogel compositions are typically obtained after removing solvents from the various gel materials disclosed herein. The aerogel compositions thus obtained may also be subjected to other processing or treatments. The various gel materials may also be subjected to other processing or treatments that are otherwise known or useful in the art before solvent removal (or liquid extraction or drying).

[0076] In the context of the present disclosure, the term "monolithic" refers to an aerogel material in which the majority of the aerogel (by weight) contained in the aerogel material or composition is in the form of a single interconnected aerogel nanostructure. Monolithic aerogel materials include aerogel materials that are initially formed to have a single interconnected gel or aerogel nanostructure, but which are subsequently broken, fractured or split into non-single aerogel nanostructures. Monolithic aerogel materials are different from particulate aerogel materials. The term "particulate aerogel material" refers to an aerogel material in which the majority of the aerogel (by weight) contained in the aerogel material is in the form of particles, particles, granules, beads or powders, which can be merged or compressed together, but lack the interconnected aerogel nanostructures between individual particles.

[0077] In the context of the present disclosure, the term "wet gel" refers to a gel in which the mobile interstitial phase within the interconnected pore network consists primarily of a liquid, such as a conventional solvent, a liquefied gas, such as liquid carbon dioxide, or a combination thereof. Aerogels typically require initial production of a wet gel followed by innovative processing and extraction to replace the mobile interstitial liquid in the gel with air. Examples of wet gels include, but are not limited to, alcogels, hyfrogels, ketogels, carbonogels, and any other wet gels known to those skilled in the art.

[0078] Aerogel compositions of the present disclosure may include reinforced aerogel compositions. In the context of the present disclosure, the term "reinforced aerogel composition" refers to an aerogel composition comprising a reinforcing phase in an aerogel material, wherein the reinforcing phase is not a part of the aerogel framework itself. The reinforcing phase can be any material that provides improved flexibility, elasticity, compliance or structural stability for the aerogel material. Examples of well-known reinforcing materials include, but are not limited to, open cell macroporous framework reinforcing materials, closed cell macroporous framework reinforcing materials, open cell membranes, honeycomb reinforcing materials, polymer reinforcing materials, and fiber-reinforced materials such as discrete fibers, textile materials, non-woven materials, needle-shaped non-woven fabrics, cotton wool, meshes, pads and felts.

[0079] In the context of the present disclosure, the term "fiber-reinforced aerogel composition" refers to a reinforced aerogel composition comprising a fiber reinforcement as a reinforcing phase. Examples of fiber reinforcements include, but are not limited to, discrete fibers, textile materials, non-woven materials, batting, batting, mesh, mat, felt, and combinations thereof. Fiber reinforcements may include a range of materials including, but are not limited to, polyesters, polyolefin terephthalates, polyethylene naphthalate, polycarbonates (examples are rayon, nylon), cotton (e.g., lycra manufactured by DuPont), carbon (e.g., graphite), polyacrylonitrile (PAN), oxidized PAN, uncarbonized heat-treated PAN (such as those produced by SGL carbon), glass or fiberglass-based materials (such as S-glass, 901 glass, 902 glass, 475 glass, E-glass), silica-based fibers such as quartz (e.g., Quartz fiber manufactured by Saint-Gobain), Q-blanket (manufactured by Johns Manville), Saffil (manufactured by Saffil), Durablanket (manufactured by Unifrax) and other silica fibers, Duraback (manufactured by Carborundum), polyaramid fibers such as Kevlar, Nomex, Sontera (all manufactured by DuPont), Conex (manufactured by Taijin), polyolefins such as Tyvek (manufactured by DuPont), Dyneema (manufactured by DSM), Spectra (manufactured by Honeywell), other polypropylene fibers such as Typar, Xavan (both manufactured by DuPont), fluoropolymers such as PTFE sold under the trade name Teflon (manufactured by DuPont), Goretex (manufactured by WLGORE), silicon carbide fibers such as Nicalon (manufactured by COI Ceramics), ceramic fibers such as Nextel (produced by 3M), acrylic polymers, wool, silk, linen, leather, suede fibers, PBO-Zylon fibers (produced by Tyobo), liquid crystal materials such as Vectan (produced by Hoechst), Cambrelle fibers (produced by DuPont), polyurethanes, polyimides, wood fibers, boron, aluminum, iron, stainless steel fibers and other thermoplastic materials such as PEEK, PES, PEI, PEK, PPS. Glass or fiberglass-based fiber reinforcements can be produced using one or more techniques. In certain embodiments, it is desirable to prepare them using carding and cross-lapping or air-laid methods. In exemplary embodiments, carding and cross-lapping glass or fiberglass-based fiber reinforcements provide certain advantages over air-laid materials.For example, for a given basis weight of reinforcement material, a carded and cross-ply glass or fiberglass-based fiber reinforcement material can provide a consistent material thickness. In certain other embodiments, it is desirable to further needle-puncture the fiber reinforcement material to interweave the fibers in the z-direction to enhance mechanical and other properties in the final aerogel composition.

[0080] The reinforced aerogel compositions of the present disclosure may include aerogel compositions reinforced with an open cell macroporous framework material. In the context of the present disclosure, the term "open cell macroporous framework" or "OCMF" refers to a porous material comprising a framework of interconnected structures having a substantially uniform composition, having a corresponding interconnected pore network integrated within the framework; and characterized by an average pore size in the range of about 10 μm to about 700 μm. Such average pore size can be measured by known techniques, including but not limited to microscopy with optical analysis. The OCMF materials of the present disclosure therefore include any open cell material that meets the definition elements described in this paragraph, including compounds that can be further classified as foams, foam-like materials, macroporous materials, etc. OCMF materials can be distinguished from materials that include a framework of interconnected structures, the interconnected structures having a void volume within the framework and not having a uniform composition, such as a collection of fibers and binders having a void volume within a fiber matrix.

[0081] In the context of the present disclosure, the term "substantially homogeneous composition" means that the homogeneity of the composition of the referenced material is within a tolerance of 10%.

[0082] In the context of the present disclosure, the term "OCMF-reinforced aerogel composition" refers to a reinforced aerogel composition comprising an open cell macroporous framework material as a reinforcing phase. OCMF materials suitable for use in the present disclosure include, but are not limited to, OCMF materials made of organic polymer materials. Examples include OCMF materials made of polyolefins, polyurethanes, phenolic resins, melamine, cellulose acetate, and polystyrene. In the context of the present disclosure, the term "organic OCMF" refers to an OCMF material having a framework consisting primarily of an organic polymer material. In certain embodiments, OCMF materials made of melamine or melamine derivatives are also preferred. In the context of the present disclosure, the term "melamine OCMF" or "melamine-based OCMF" refers to an organic OCMF material having a framework consisting primarily of a polymer material derived from the reaction of melamine with a condensation agent, such as formaldehyde. Examples of OCMF materials made of melamine or melamine derivatives for use in the present disclosure are provided in U.S. Pat. Nos. 8,546,457, 4,666,948, and WO 2001 / 094436. The term "inorganic OCMF" refers to an OCMF material having a framework composed primarily of an inorganic material. Examples of inorganic OCMFs include, but are not limited to, cementous materials, gypsum, and calcium silicate.

[0083] In the context of the present disclosure, the term "foam" refers to a material comprising a framework of interconnected polymer structures of substantially uniform composition, having a network or collection of corresponding pores integrated within the framework, and the material is formed by distributing a portion of the gas in the form of bubbles in a liquid or resin foam material, so that when the foam material is cured into a solid structure, the bubbles are retained as pores. Generally, a variety of methods can be used to make foams-see, for example, U.S. Patent Nos. 6,147,134, 5,889,071, 6,187,831, and 5,229,429. The foam materials of the present disclosure therefore include any material that meets the definition elements described in this paragraph, including compounds that can be further classified as OCMF materials, macroporous materials, etc. The foams as defined in the present disclosure can be thermoplastic, elastomer, and thermosetting (duromer) types.

[0084] The pores within the solid framework may also be referred to as "cells". The chambers may be separated by chamber walls or membranes, thereby forming a group of independent closed pores within the porous material. The term "closed cell" refers to a porous material in which at least 50% of the pore volume is [substantially] a restricted chamber surrounded by a membrane or wall. The chambers in the material may also be interconnected by chamber openings, thereby forming a network of interconnected open pores within the material. The term "open cell" refers to a porous material in which at least 50% of the pore volume is an open chamber. The open chamber material may include a mesh open chamber material, a non-mesh open chamber material, or a combination thereof. The mesh material is an open chamber material produced by a meshing method that eliminates or pierces the chamber membrane within the porous material. The mesh material generally has a higher open chamber concentration than the non-mesh material, but is often more expensive and more difficult to produce. In general, no porous material has completely one type of chamber structure (open chamber or closed chamber). A variety of methods can be used to prepare porous materials, including the foam production methods provided in US Pat. Nos. 6,147,134, 5,889,071, 6,187,831, 5,229,429, 4,454,248, and US Patent Application No. 2007 / 0213417.

[0085] In the context of the present disclosure, the term "aerogel blanket" or "aerogel blanket composition" refers to an aerogel composition reinforced with a continuous sheet of reinforcing material. Aerogel blanket compositions can be distinguished from other reinforced aerogel compositions reinforced with discontinuous reinforcing materials, such as separate agglomerates or blocks of reinforcing materials. Aerogel blanket compositions are particularly useful for applications requiring flexibility because they are highly conformable and can be used like a blanket to cover surfaces of simple or complex geometries while retaining the excellent thermal insulation properties of the aerogel.

[0086] In the context of the present disclosure, the terms "flexible" and "flexibility" refer to the ability of an aerogel material or composition to be bent or flexed without macrostructural failure. The aerogel composition of the present disclosure is capable of bending at least 5°, at least 25°, at least 45°, at least 65°, or at least 85° without macrostructural failure; and / or having a bending radius of less than 4 feet, less than 2 feet, less than 1 foot, less than 6 inches, less than 3 inches, less than 2 inches, less than 1 inch, or less than 1 / 2 inch, without macrostructural failure. Similarly, the terms "highly flexible" or "highly flexible" refer to an aerogel material or composition capable of bending at least 90° and / or having a bending radius of less than 1 / 2 inch without macrostructural failure. In addition, the terms "classified flexible" and "classified as flexible" refer to an aerogel material or composition that can be classified as flexible according to ASTM C1101 (ASTM International, West Conshohocken, PA).

[0087] Aerogel compositions of the present disclosure may be flexible, highly flexible, and / or classified flexible. Aerogel compositions of the present disclosure may also be drapable. In the context of the present disclosure, the terms "drapable" and "drapability" refer to the ability of an aerogel material or composition to bend or bend to 90° or greater with a radius of curvature of about 4 inches or less without macroscopic failure. Aerogel materials or compositions according to certain embodiments of the present disclosure are flexible, so that the composition is non-rigid and can be applied to a three-dimensional surface or object and conformable, or can be prefabricated into a variety of shapes and configurations to simplify installation or application.

[0088] In the context of the present disclosure, the term "additive" or "additive element" refers to a material that can be added to an aerogel composition before, during, or after the production of an aerogel. Additives can be added to change or improve the desired properties in the aerogel, or to offset undesirable properties in the aerogel. Additives are typically added to the aerogel material before gelation into a precursor liquid, during gelation into a transitional state material, or after gelation into a solid or semi-solid material. Examples of additives include, but are not limited to, microfibers, fillers, reinforcing agents, stabilizers, thickeners, elastic compounds, sunscreens, coloring or dyeing compounds, radiation absorbing compounds, radiation reflecting compounds, fire additives, corrosion inhibitors, thermally conductive components, components that provide heat capacity, phase change materials, pH adjusters, redox adjusters, HCN moderators, exhaust moderators, conductive compounds, dielectric compounds, magnetic compounds, radar blocking components, hardeners, anti-shrinkage agents, and other aerogel additives known to those skilled in the art. In some embodiments, the component that provides heat capacity may include a material having a specific heat capacity of at least about 0.3 J / (gC). In some embodiments, the material providing heat capacity has a specific heat capacity of at least about 0.5 J / (gC). For example, the material providing heat capacity may include a metal such as aluminum, titanium, nickel, steel, iron, or a combination thereof. In some embodiments, the thermal control member or battery thermal management member may include a material layer or coating that provides heat capacity. In some embodiments, the thermal control member or battery thermal management member may include particles of a material that provides heat capacity arranged within a layer of the thermal control member or battery thermal management member. In certain embodiments, the thermal control member or battery thermal management member may include at least one material layer that provides heat capacity arranged adjacent to the aerogel composition. In certain embodiments, the thermal control member or battery thermal management member may include at least one layer of material that provides heat capacity arranged between at least two layers in a multilayer aerogel composition.

[0089] In certain embodiments, the aerogel compositions, reinforced aerogel compositions, and thermal control components or battery thermal management components disclosed herein can function during a high temperature event, for example, to provide thermal protection during a high temperature event as disclosed herein. A high temperature event is characterized by at least about 1 cm 2 At least about 25 kW / m2 over an area of 2 , at least about 30kW / m 2 , at least about 35kW / m 2 Or at least about 40kW / m 2 Heat flux. About 40kW / m 2The heat flux is related to the heat flux produced by a typical flame (Behavior of Charring Solids under Fire-Level Heat Fluxes; Milosavljevic, I., Suuberg, EM; NISTIR 5499; September 1994). In special cases, high temperature events are at least about 10 cm 2 A heat flux of about 40 kW / m2 over an area sustained for at least 1 minute.

[0090] In the context of the present disclosure, the terms "thermal conductivity" and "TC" refer to a measure of the ability of a material or composition to transfer heat between two surfaces on either side of the material or composition, where there is a temperature difference between the two surfaces. Thermal conductivity is specifically measured as the heat energy transferred per unit time and per unit surface area divided by the temperature difference. It is usually recorded in SI units as mW / m*K (milliwatts per meter*Kelvin). The thermal conductivity of a material may be determined by test methods known in the art, including, but not limited to, Test Method for Steady State Heat Transfer Properties by Heat Flow Meter Apparatus (ASTM C518, ASTM International, West Conshohocken, PA); Test Method for Steady State Heat Flux Measurement and Heat Transfer Properties by Guarded Hot Plate Apparatus (ASTM C177, ASTM International, West Conshohocken, PA); Test Method for Steady State Heat Transfer Properties of Pipe Insulation (ASTM C335, ASTM International, West Conshohocken, PA); Thin Heater Thermal Conductivity Test (ASTM C1114, ASTM International, West Conshohocken, PA); Standard Test Method for Thermal Transfer Properties of Thermally Conductive Electrical Insulating Materials (ASTM D5470, ASTM International, West Conshohocken, PA); Determination of Thermal Resistance by Guarded Hot Plate and Heat Flow Meter Method (EN 12667, British Standards Institution, United Kingdom); or Determination of Steady State Thermal Resistance and Related Properties - Guarded Hot Plate Apparatus (ISO 8203, International Organization for Standardization). Standardization, Switzerland). Because different methods may lead to different results, it should be understood that in the context of the present disclosure and unless otherwise explicitly stated, the measurements of thermal conductivity are obtained according to the ASTM C518 standard (Test method for steady-state heat transfer properties by heat flow meter equipment) at a temperature of about 37.5°C, at atmospheric pressure in the surrounding environment, and under a compressive load of about 2 psi. The measurement results reported according to ASTM C518 generally correlate well with any measurement results according to EN 12667 with any relevant adjustments for the compressive load. In certain embodiments, the thermal conductivity of the aerogel materials or compositions of the present disclosure is about 40 mW / mK or less, about 30 mW / mK or less, about 25 mW / mK or less, about 20 mW / mK or less, about 18 mW / mK or less, about 16 mW / mK or less, about 14 mW / mK or less, about 12 mW / mK or less, about 10 mW / mK or less, about 5 mW / mK or less, or a range between any two of these values.

[0091] Thermal conductivity measurements can also be obtained at a temperature of about 10°C, at atmospheric pressure, under compression. The thermal conductivity measurements at 10°C are typically 0.5-0.7 mW / mK lower than the corresponding thermal conductivity measurements at 37.5°C. In certain embodiments, the thermal conductivity of the aerogel material or composition of the present disclosure at 10°C is about 40 mW / mK or less, about 30 mW / mK or less, about 25 mW / mK or less, about 20 mW / mK or less, about 18 mW / mK or less, about 16 mW / mK or less, about 14 mW / mK or less, about 12 mW / mK or less, about 10 mW / mK or less, about 5 mW / mK or less, or in a range between any two of these values.

[0092] In the context of this disclosure, the term "density" refers to a measurement of the mass of an aerogel material or composition per unit volume. The term "density" generally refers to the apparent density of an aerogel material and the bulk density of an aerogel composition. Density is usually reported as kg / m 3 or g / cc. The density of an aerogel material or composition may be determined by methods known in the art, including, but not limited to, Standard Test Methods for Size and Density of Preformed Block and Board Type Insulation (ASTM C303, ASTM International, West Conshohocken, PA); Standard Test Methods for Thickness and Density of Blanket or Batt Insulation (ASTM C167, ASTM International, West Conshohocken, PA); Determination of Apparent Density of Preformed Pipe Insulation (EN 13470, British Standards Institution, United Kingdom); or Determination of Apparent Density of Preformed Pipe Insulation (ISO 18098, International Organization for Standardization, Switzerland). Because different methods may lead to different results, it should be understood that in the context of this disclosure, unless otherwise specified, density measurements are obtained by thickness measurements under 2 psi compression according to ASTM C167 (Standard Test Methods for Thickness and Density of Blanket or Batt Insulation). In certain embodiments, the aerogel material or composition of the present disclosure has a density of about 0.60 g / cc or less, about 0.50 g / cc or less, about 0.40 g / cc or less, about 0.30 g / cc or less, about 0.25 g / cc or less, about 0.20 g / cc or less, about 0.18 g / cc or less, about 0.16 g / cc or less, about 0.14 g / cc or less, about 0.12 g / cc or less, about 0.10 g / cc or less, about 0.05 g / cc or less, about 0.01 g / cc or less, or in a range between any two of these values.

[0093] In the context of the present disclosure, the term "hydrophobicity" refers to a measure of the ability of an aerogel material or composition to repel water.

[0094] The hydrophobicity of an aerogel material or composition can be expressed in terms of liquid water uptake. In the context of the present disclosure, the term "liquid water uptake" refers to a measurement of the potential of an aerogel material or composition to absorb or otherwise retain liquid water. Liquid water uptake can be expressed as the percentage of water (by weight or volume) absorbed or otherwise retained by an aerogel material or composition when exposed to liquid water under certain measurement conditions. Liquid water uptake of an aerogel material or composition can be determined by methods known in the art, including but not limited to Standard Test Method for Determining Water Retention (Repellency) of Fiberglass Insulation (ASTM C1511, ASTM International, West Conshohocken, PA); Standard Test Method for Water Uptake by Immersed Insulation Materials (ASTM C1763, ASTM International, West Conshohocken, PA); Insulation Products for Building Applications: Determination of Short-Term Water Uptake by Partial Immersion (EN1609, British Standards Institution, United Kingdom). Because different methods may lead to different results, unless otherwise stated, it should be understood that in the context of the present disclosure, the measured values ​​of liquid water absorption are obtained according to the ASTM C1511 standard (Standard Test Method for Determining Water Retention (Repellency) of Glass Fiber Insulation) at ambient pressure and temperature. In certain embodiments, the aerogel materials or compositions of the present disclosure may have a liquid water absorption of about 50 wt% or less, about 40 wt% or less, about 30 wt% or less, about 20 wt% or less, about 15 wt% or less, about 10 wt% or less, about 8 wt% or less, about 3 wt% or less, about 2 wt% or less, about 1 wt% or less, about 0.1 wt% or less, or a range between any two of these values. An aerogel material or composition having improved liquid water absorption relative to another aerogel material or composition will have a lower liquid water absorption / retention percentage relative to a reference aerogel material or composition.

[0095] The hydrophobicity of an aerogel material or composition can be expressed in terms of water vapor absorption. In the context of the present disclosure, the term "water vapor absorption" refers to a measure of the potential of an aerogel material or composition to absorb water vapor. Water vapor absorption can be expressed as the percentage (by weight) of water absorbed or retained by an aerogel material or composition when exposed to water vapor under certain measurement conditions. Water vapor absorption of an aerogel material or composition can be determined by methods known in the art, including but not limited to Standard Test Method for Determining Water Vapor Sorption of Unfaced Mineral Fiber Insulation (ASTM C1104, ASTM International, West Conshohocken, PA); Insulation Products for Building Applications: Determination of Long-Term Water Absorption by Diffusion (EN 12088, British Standards Institution, United Kingdom). Because different methods may lead to different results, unless otherwise stated, it should be understood that in the context of the present disclosure, the measured values ​​of water vapor absorption are obtained according to the ASTM C1104 standard (Standard Test Method for Determining Water Vapor Sorption of Unfaced Mineral Fiber Insulation) at ambient pressure, 49°C and 95% humidity for 24 hours (modified from 96 hours according to the ASTM C1104 standard). In certain embodiments, the aerogel materials or compositions of the present disclosure may have a water vapor absorption of about 50 wt% or less, about 40 wt% or less, about 30 wt% or less, about 20 wt% or less, about 15 wt% or less, about 10 wt% or less, about 8 wt% or less, about 3 wt% or less, about 2 wt% or less, about 1 wt% or less, about 0.1 wt% or less, or a range between any two of these values. An aerogel material or composition having improved water vapor absorption relative to another aerogel material or composition will have a lower water vapor absorption / retention percentage relative to a reference aerogel material or composition.

[0096] The hydrophobicity of an aerogel material or composition can be represented by measuring the equilibrium contact angle of a water droplet at the interface with the surface of the material. The aerogel material or composition of the present disclosure can have a water contact angle of about 90° or greater, about 120° or greater, about 130° or greater, about 140° or greater, about 150° or greater, about 160° or greater, about 170° or greater, about 175° or greater, or a range between any two of these values.

[0097] In the context of this disclosure, the terms “heat of combustion,” “HOC,” and “ΔH C" refers to a measurement of the amount of heat energy released in the combustion or exothermic decomposition of a material or composition. The heat of combustion is usually recorded as calories (cal / g) of heat energy released per gram of aerogel material or composition, or as million joules (MJ / kg) of heat energy released per kilogram of material or composition. The heat of combustion of a material or composition can be determined by methods known in the art, including but not limited to the determination of the reaction-gross heat of combustion (caloric value) for product fire testing (EN ISO 1716, International Organization for Standardization, Switzerland; adopted by EN). In the context of the present disclosure, unless otherwise stated, the heat of combustion is determined according to EN ISO The measured value of the heat of combustion is obtained according to the 1716 standard (Determination of the reaction-gross heat of combustion (caloric value) for product fire testing). In certain embodiments, the aerogel composition of the present disclosure can have a heat of combustion of about 750 cal / g or less, about 717 cal / g or less, about 700 cal / g or less, about 650 cal / g or less, about 600 cal / g or less, about 575 cal / g or less, about 550 cal / g or less, about 500 cal / g or less, about 450 cal / g or less, about 400 cal / g or less, about 350 cal / g or less, about 30 ...50 cal / g or less, about 300 cal / g or less, about 350 cal / g or less, about 300 cal / g or less, about 300 cal / g or less, about 350 cal / g or less, about 300 cal / g or less, about 350 cal / g or less, about 3 1 / g or less, about 250 cal / g or less, about 200 cal / g or less, about 150 cal / g or less, about 100 cal / g or less, about 50 cal / g or less, about 25 cal / g or less, about 10 cal / g or less, or a range between any two of these values. An aerogel composition having an improved heat of combustion relative to another aerogel composition will have a lower heat of combustion value relative to a reference aerogel composition. In certain embodiments of the present disclosure, the HOC of an aerogel composite is improved by incorporating a pyrolytic additive into the aerogel composite.

[0098] In the context of this disclosure, all thermal analyses and related definitions are referred to using measurements made at ambient pressure, in air, starting at 25° C. and ramping to 1000° C. at a rate of 20° C. per minute. Therefore, any changes to these parameters will have to be taken into account (or re-performed under these conditions) in measuring and calculating thermal decomposition onset, peak exotherm temperature, peak endotherm temperature, etc.

[0099] In the context of this disclosure, the terms "thermal decomposition onset" and "T D" refers to a measurement of the lowest temperature of ambient heat at which a rapidly exothermic reaction from decomposition of an organic material occurs within a material or composition. The onset of thermal decomposition of an organic material within a material or composition can be measured using thermogravimetric analysis (TGA). A TGA curve for a material depicts the weight loss (mass %) of the material when exposed to an increase in ambient temperature, and is therefore indicative of thermal decomposition. The onset of thermal decomposition of a material can be related to the intersection of the following tangent lines to the TGA curve: a line tangent to the baseline of the TGA curve, and a line tangent to the TGA curve at the point of maximum slope during a rapidly exothermic decomposition event associated with decomposition of the organic material. In the context of the present disclosure, unless otherwise stated, the TGA analysis provided in this paragraph is used to obtain measurements of the onset of thermal decomposition of an organic material.

[0100] The onset of thermal decomposition of a material can also be measured using differential scanning calorimetry (DSC) analysis. The DSC curve of a material depicts the heat energy (mW / mg) released when the material is exposed to gradually increasing ambient temperatures. The onset of thermal decomposition temperature of a material can be associated with the point in the DSC curve where the ΔmW / mg (change in thermal energy output) increases the most, thus representing the exothermic generation from the aerogel material. In the context of the present disclosure, unless otherwise explicitly stated, a heating rate of 20°C / min as further defined in the preceding paragraph is used to obtain measurements of the onset of thermal decomposition using DSC, TGA, or both. DSC and TGA each provide similar values ​​for this onset of thermal decomposition, and most of the time, the tests are performed simultaneously, so results are obtained from both. In certain embodiments, the aerogel materials or compositions of the present disclosure have a thermal decomposition onset of about 300°C or more, about 320°C or more, about 340°C or more, about 360°C or more, about 380°C or more, about 400°C or more, about 420°C or more, about 440°C or more, about 460°C or more, about 480°C or more, about 500°C or more, about 550°C or more, about 600°C or more, or within a range between any two of these values. In the context of the present disclosure, for example, a first composition having a higher thermal decomposition onset than a second composition would be considered an improvement of the first composition relative to the second composition. As contemplated herein, when one or more pyrotechnic additives are added, the onset of thermal decomposition of the composition or material is increased compared to a composition that does not include any pyrotechnic additives.

[0101] In the context of this disclosure, the terms "endothermic decomposition onset" and "T ED" refers to a measurement of the lowest temperature of the ambient heat at which an endothermic reaction from decomposition or dehydration occurs within a material or composition. The onset of endothermic decomposition of a material or composition can be measured using thermogravimetric analysis (TGA). A TGA curve of a material depicts the weight loss (mass %) of the material when exposed to an increase in ambient temperature. The onset of thermal decomposition of a material can be related to the intersection of the following tangent lines to the TGA curve: a line tangent to the baseline of the TGA curve, and a line tangent to the TGA curve at the point of maximum slope during the rapid endothermic decomposition or dehydration of the material. In the context of the present disclosure, unless otherwise stated, the measurement of the onset of endothermic decomposition of a material or composition is obtained using TGA analysis as provided in this paragraph.

[0102] In the context of this disclosure, the terms "furnace temperature rise" and "ΔT R ” refers to the maximum temperature (T MAX ) relative to the material or composition under thermal decomposition conditions (usually the final temperature or T FIN ). The furnace temperature rise is usually recorded in degrees Celsius or ° C. The furnace temperature rise of a material or composition can be determined by methods known in the art, including but not limited to the reaction for fire testing of buildings and transportation products: non-combustibility test (EN ISO 1182, International Organization for Standardization, Switzerland; EN adopted). In the context of the present disclosure, unless otherwise stated, the measurement of the furnace temperature rise is obtained according to conditions comparable to the EN ISO 1182 standard (reaction for fire testing of buildings and transportation products: non-combustibility test). In certain embodiments, the aerogel compositions of the present disclosure may have an oven temperature rise of about 100°C or less, about 90°C or less, about 80°C or less, about 70°C or less, about 60°C or less, about 50°C or less, about 45°C or less, about 40°C or less, about 38°C or less, about 36°C or less, about 34°C or less, about 32°C or less, about 30°C or less, about 28°C or less, about 26°C or less, about 24°C or less, or a range between any two of these values. In the context of composition stability at high temperatures, for example, an oven temperature rise of a first composition that is lower than an oven temperature rise of a second composition would be considered an improvement of the first composition relative to the second composition. As contemplated herein, the oven temperature rise of a composition is reduced when one or more pyrotechnic additives are added compared to a composition that does not include any pyrotechnic additives.

[0103] In the context of this disclosure, the terms "flame time" and "T 火焰" refers to the measurement of the sustained flame of a material or composition under thermal decomposition conditions, where "sustained flame" refers to the duration of a flame on any portion of the visible portion of the specimen for 5 seconds or more. Flame time is usually recorded in seconds or minutes. The flame time of a material or composition can be determined by methods known in the art, including but not limited to the reaction for fire testing of buildings and transportation products: non-combustibility test (EN ISO 1182, International Organization for Standardization, Switzerland; adopted by EN). In the context of this disclosure, unless otherwise stated, the flames are described in accordance with EN ISO Flame time measurements are obtained under conditions comparable to the 1182 standard (Reaction to fire testing of buildings and transportation products: Non-combustible test). In certain embodiments, the aerogel compositions of the present disclosure have a flame time of about 30 seconds or less, about 25 seconds or less, about 20 seconds or less, about 15 seconds or less, about 10 seconds or less, about 5 seconds or less, about 2 seconds or less, or a range between any two of these values. In the context of this article, for example, a first composition having a shorter flame time than a second composition would be considered an improvement of the first composition relative to the second composition. As contemplated herein, when one or more fire additives are added, the flame time of the composition is shortened compared to a composition that does not include any fire additive.

[0104] In the context of the present disclosure, the terms "mass loss" and "ΔM" refer to the measurement of the amount of a material, composition or composite material that is lost or burned under thermal decomposition conditions. Mass loss is usually recorded as a weight percentage or wt%. The mass loss of a material, composition or composite material can be determined by methods known in the art, including but not limited to the reaction for fire testing of buildings and transportation products: non-combustibility test (EN ISO 1182, International Organization for Standardization, Switzerland; EN adopted). In the context of the present disclosure, unless otherwise stated, the measurement of mass loss is obtained according to conditions equivalent to the EN ISO 1182 standard (reaction for fire testing of buildings and transportation products: non-combustibility test). In certain embodiments, the aerogel composition of the present disclosure may have a mass loss of about 50% or less, about 40% or less, about 30% or less, about 28% or less, about 26% or less, about 24% or less, about 22% or less, about 20% or less, about 18% or less, about 16% or less, or in a range between any two of these values. In the context of this article, for example, a first composition that loses less mass than a second composition would be considered an improvement of the first composition relative to the second composition. As contemplated herein, a composition has a reduced mass loss when one or more fire additives are added, compared to a composition that does not include any fire additives.

[0105] In the context of the present disclosure, the term "peak exothermic temperature" refers to a measurement of the temperature of the ambient heat at which the exothermic heat release from decomposition is maximum. The peak exothermic temperature of a material or composition can be measured using TGA analysis, differential scanning calorimetry (DSC), or a combination thereof. DSC and TGA will provide similar values ​​for the peak exothermic temperature, respectively, and in most cases, the tests are performed simultaneously, so results are obtained from both. In a typical DSC analysis, heat flow is plotted against rising temperature, and the peak exothermic temperature is the temperature at which the highest peak appears in the curve. In the context of the present disclosure, unless otherwise stated, the measurement of the peak exothermic temperature of a material or composition is obtained using a TGA analysis as provided in this paragraph.

[0106] In the context of endothermic materials, the term "peak endothermic temperature" refers to a measurement of the temperature of the ambient heat when the endothermic heat absorption from decomposition is minimal. The peak endothermic temperature of a material or composition can be measured using TGA analysis, differential scanning calorimetry (DSC), or a combination thereof. In a typical DSC analysis, heat flow is plotted versus rising temperature, and the peak endothermic temperature is the temperature at which the lowest peak appears in the curve. In the context of the present disclosure, unless otherwise stated, a TGA analysis as provided in this paragraph is used to obtain a measurement of the peak endothermic temperature of a material or composition.

[0107] In the context of the present disclosure, the terms "low flammability" and "low flammable" refer to materials or compositions that meet a combination of the following properties: i) a furnace temperature rise of 50°C or less; ii) a flame time of 20 seconds or less; and iii) a mass loss of 50 wt% or less. In the context of the present disclosure, the terms "non-flammability" and "non-combustible" refer to materials or compositions that meet a combination of the following properties: i) a furnace temperature rise of 40°C or less; ii) a flame time of 2 seconds or less; and iii) a mass loss of 30 wt% or less. As described herein, it is contemplated that when one or more fire additives are included, the flammability (e.g., a combination of furnace temperature rise, flame time, and mass loss) of the composition is reduced.

[0108] In the context of the present disclosure, the terms "low flammability" and "low combustion" refer to low combustible materials or compositions having a total heat of combustion (HOC) less than or equal to 3 MJ / kg. In the context of the present disclosure, the terms "non-combustible" and "non-combustible" refer to non-combustible materials or compositions having a heat of combustion (HOC) less than or equal to 2 MJ / kg. As described herein, it is contemplated that when one or more fire additives are included, the HOC of the composition is reduced.

[0109] Aerogels are described as frameworks of interconnected structures, most commonly composed of interconnected oligomeric, polymeric, or colloidal particles. Aerogel frameworks can be made from a range of precursor materials, including inorganic precursor materials (such as those used in the production of silica-based aerogels); organic precursor materials (such as those used in the production of carbon-based aerogels); hybrid inorganic / organic precursor materials; and combinations thereof. In the context of the present disclosure, the term "amalgam aerogel" refers to an aerogel produced by a combination of two or more different gel precursors; the corresponding precursors are referred to as "amalgam precursors."

[0110] Inorganic aerogels are usually formed from metal oxides or metal alkoxide materials. Metal oxides or metal alkoxide materials can be based on oxides or alkoxides of any metal that can form oxides. These metals include, but are not limited to, silicon, aluminum, titanium, zirconium, hafnium, yttrium, vanadium, cerium, etc. Inorganic silica aerogels are usually prepared by hydrolysis and condensation of silica-based alkoxides (such as tetraethoxysilane) or by gelation of silicic acid or water glass. Other relevant inorganic precursor materials for the synthesis of silica-based aerogels include, but are not limited to, metal silicates such as sodium silicate or potassium silicate, alkoxysilanes, partially hydrolyzed alkoxysilanes, tetraethoxysilane (TEOS), partially hydrolyzed TEOS, condensates of TEOS, tetramethoxysilane (TMOS), partially hydrolyzed TMOS, condensates of TMOS, tetra-n-propoxysilane, partial hydrolysis and / or condensates of tetra-n-propoxysilane, polyethyl silicate, partially hydrolyzed polyethyl silicate, monomeric alkylalkoxysilanes, bistrialkoxyalkyl or aryl silanes, polyhedral silsesquioxanes, or combinations thereof.

[0111] In certain embodiments of the present disclosure, pre-hydrolyzed TEOS, such as Silbond H-5 (SBH5, Silbond Corp) (which is hydrolyzed at a water / silicon dioxide ratio of about 1.9-2) can be used as commercially available or can be further hydrolyzed before incorporation into the gelation process. Partially hydrolyzed TEOS or TMOS, such as polyethyl silicate (Silbond 40) or polymethyl silicate can also be used as commercially available or can be further hydrolyzed before incorporation into the gelation process.

[0112] Inorganic aerogels may also include gel precursors containing at least one hydrophobic group, such as alkyl metal alkoxides, cycloalkyl metal alkoxides, and aryl metal alkoxides, which may impart or improve certain properties in the gel, such as stability and hydrophobicity. Inorganic silica aerogels may specifically include hydrophobic precursors, such as alkyl silanes or aryl silanes. Hydrophobic gel precursors may be used as the primary precursor material to form the framework of the gel material. However, in forming amalgam aerogels, hydrophobic gel precursors are more commonly combined with simple metal alkoxides to serve as co-precursors. Hydrophobic inorganic precursor materials for the synthesis of silica-based aerogels include, but are not limited to, trimethylmethoxysilane (TMS), dimethyldimethoxysilane (DMS), methyltrimethoxysilane (MTMS), trimethylethoxysilane, dimethyldiethoxysilane (DMDS), methyltriethoxysilane (MTES), ethyltriethoxysilane (ETES), diethyldiethoxysilane, dimethyldiethoxysilane (DMDES), ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane (PhTES), hexamethyldisilazane, and hexaethyldisilazane, etc. Any derivative of any of the above precursors may be used, and in particular, certain polymers of other chemical groups may be added or cross-linked to one or more of the above precursors.

[0113] Aerogels can also be treated to impart or improve hydrophobicity. Hydrophobic treatment can be applied to sol-gel solutions, wet gels before liquid extraction, or aerogels after liquid extraction. Hydrophobic treatment is particularly common in the production of metal oxide aerogels, such as silica aerogels. Examples of hydrophobic treatments of gels will be discussed in more detail below, specifically in the context of treating silica wet gels. However, the specific examples and descriptions provided herein are not intended to limit the scope of the present disclosure to any specific type of hydrophobic treatment procedures or aerogel substrates. The present disclosure may include any gel or aerogel known to those skilled in the art, as well as methods for hydrophobic treatment of aerogels in wet gel form or dry aerogel form.

[0114] The hydrophobic treatment is performed by reacting the hydroxyl moieties on the gel, such as the silanol groups (Si-OH) present on the silica gel framework, with the functional groups of the hydrophobic agent. The resulting reaction converts the silanol groups and the hydrophobic agent into hydrophobic groups on the silica gel framework. The hydrophobic agent compound can react with the hydroxyl groups on the gel according to the following reaction: R N MX 4-N (Hydrophobic agent) + MOH (Silanol) → MOMR N (Hydrophobic group) + HX. The hydrophobic treatment can be performed on the external macroscopic surface of the silica gel or on the internal pore surfaces within the porous network of the gel.

[0115] The gel can be immersed in a mixture of a hydrophobic agent and an optional hydrophobic treatment solvent in which the hydrophobic agent is soluble and which is also miscible with the gel solvent in the wet gel. A variety of hydrophobic treatment solvents can be used, including solvents such as methanol, ethanol, isopropanol, xylene, toluene, benzene, dimethylformamide, and hexane. The hydrophobic agent in liquid or gaseous form can also be directly contacted with the gel to impart hydrophobicity.

[0116] The hydrophobic treatment method may include mixing or stirring to help the hydrophobic agent penetrate the wet gel. The hydrophobic treatment method may also include changing other conditions, such as temperature and pH, to further enhance and optimize the treatment reaction. After the reaction is completed, the wet gel is washed to remove unreacted compounds and reaction byproducts.

[0117] The hydrophobic agent used for hydrophobic treatment of aerogels is generally of the formula: R N MX 4-N Compound; wherein M is a metal; R is a hydrophobic group, such as CH3, CH2CH3, C6H6 or a similar hydrophobic alkyl, cycloalkyl or aryl moiety; and X is a halogen, typically Cl. Specific examples of hydrophobic agents include, but are not limited to, trimethylchlorosilane (TMCS), triethylchlorosilane (TECS), triphenylchlorosilane (TPCS), dimethylchlorosilane (DMCS), dimethyldichlorosilane (DMDCS), and the like. The hydrophobic agent may also have the formula: Y(R3M)2; wherein M is a metal; Y is a bridging group, such as NH or O; and R is a hydrophobic group, such as CH3, CH2CH3, C6H6 or a similar hydrophobic alkyl, cycloalkyl or aryl moiety. Specific examples of these hydrophobic agents include, but are not limited to, hexamethyldisilazane [HMDZ] and hexamethyldisiloxane [HMDSO]. The hydrophobic agent may also include a hydrophobic agent having the formula: R N MV 4-N A compound wherein V is a reactive group or a leaving group other than a halogen. Specific examples of these hydrophobic agents include, but are not limited to, vinyl triethoxy silane and vinyl trimethoxy silane.

[0118] The hydrophobic treatment of the present disclosure may also be performed during the removal, exchange or drying of the liquid in the gel. In a specific embodiment, the hydrophobic treatment may be performed in a supercritical fluid environment (such as but not limited to supercritical carbon dioxide) and may be combined with a drying or extraction step.

[0119] In the context of the present disclosure, the term "hydrophobic-bound silicon" refers to silicon atoms within the framework of a gel or aerogel, which contains at least one hydrophobic group covalently bonded to the silicon atoms. Examples of hydrophobic-bound silicon include, but are not limited to, silicon atoms in silica groups within a gel framework formed by a gel precursor (such as MTES or DMDS) containing at least one hydrophobic group. Hydrophobic-bound silicon may also include, but is not limited to, silicon atoms in a gel framework or on a gel surface treated with a hydrophobic agent (such as HMDZ) to impart or improve hydrophobicity by introducing other hydrophobic groups into the composition. The hydrophobic groups of the present disclosure include, but are not limited to, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, octyl, phenyl, or other substituted or unsubstituted hydrophobic organic groups known to those skilled in the art. In the context of the present disclosure, the terms "hydrophobic groups", "hydrophobic organic materials" and "hydrophobic organic content" specifically exclude readily hydrolyzable organosilicon-bonded alkoxy groups on the framework of the gel material, which are reaction products between organic solvents and silanol groups. These excluded groups are distinguishable from the hydrophobic organic content of the groups by NMR analysis. The amount of hydrophobic bonded silicon contained in the aerogel can be analyzed using NMR spectroscopy, such as CP / MAS 29 Si solid-state NMR. NMR analysis of aerogels allows for the characterization and relative quantification of M-type hydrophobically bonded silica (monofunctional silica, such as TMS derivatives); D-type hydrophobically bonded silica (difunctional silica, such as DMDS derivatives); T-type hydrophobically bonded silica (trifunctional silica, such as MTES derivatives); and Q-type silica (tetrafunctional silica, such as TEOS derivatives). NMR analysis can also be performed by classifying specific types of hydrophobically bonded silica into subtypes (e.g., classifying T-type hydrophobically bonded silica into T 1 Species, T 2 Species and T 3 Species) are used to analyze the bonding chemistry of hydrophobically bonded silicon contained in aerogels. Specific details related to NMR analysis of silica materials can be found in the article "Applications of Solid-State NMR to the Study of Organic / Inorganic Multicomponent Materials" by Geppi et al., specifically pages 7-9 (Appl. Spec. Rev. (2008), 44-1: 1-89), which is incorporated herein by reference according to the specific pages cited.

[0120] CP / MAS 29In Si NMR analysis, the characterization of hydrophobically bonded silicon can be based on the following chemical shift peaks: M 1 (30 to 10 ppm); D 1 (10 to -10ppm), D 2 (-10 to -20ppm); T 1 (-30 to -40ppm), T 2 (-40 to -50ppm), T 3 (-50 to -70ppm); Q 2 (-70 to -85ppm), Q 3 (-85 to -95ppm), Q 4 (-95 to -110 ppm). These chemical shift peaks are approximate and exemplary and are not intended to be limiting or definitive. The exact chemical shift peaks attributable to the various silicon species within the material may depend on the specific chemical composition of the material and can generally be explained by routine experimentation and analysis by those skilled in the art.

[0121] In the context of the present disclosure, the term "hydrophobic organic content" or "hydrophobe content" or "hydrophobic content" refers to the amount of hydrophobic organic material bonded to the framework in an aerogel material or composition. The hydrophobic organic content of an aerogel material or composition can be expressed as the weight percentage of the amount of hydrophobic organic material on the aerogel framework relative to the total amount of material in the aerogel material or composition. The hydrophobic organic content can be calculated by one skilled in the art based on the properties and relative concentrations of the materials used in producing the aerogel material or composition. The hydrophobic organic content can also be measured using thermogravimetric analysis (TGA) of the subject material, preferably in an oxygen atmosphere (although TGA under an alternative gas environment is also useful). Specifically, the percentage of hydrophobic organic material in the aerogel can be correlated to the percentage weight loss of the hydrophobic aerogel material or composition when subjected to combustion heating temperatures during TGA analysis, and adjusted for water loss, residual solvent loss, and readily hydrolyzable alkoxy group loss during TGA analysis. Other alternative techniques, such as differential scanning calorimetry, elemental analysis (particularly carbon), chromatographic techniques, nuclear magnetic resonance spectroscopy, and other analytical techniques known to those skilled in the art may be used to measure and determine the hydrophobe content in the aerogel compositions of the present disclosure. In some cases, a combination of known techniques may be useful or necessary to determine the hydrophobe content of the aerogel compositions of the present disclosure.

[0122] The aerogel materials or compositions of the present disclosure can have a hydrophobic organic content of 50 wt % or less, 40 wt % or less, 30 wt % or less, 25 wt % or less, 20 wt % or less, 15 wt % or less, 10 wt % or less, 8 wt % or less, 6 wt % or less, 5 wt % or less, 4 wt % or less, 3 wt % or less, 2 wt % or less, 1 wt % or less, or a range between any two of these values.

[0123] The term "fuel content" refers to the total amount of combustible material in an aerogel material or composition, which can be related to the total percentage of weight loss in an aerogel material or composition when subjected to combustion heating temperatures during TGA or TG-DSC analysis, and adjusted for moisture loss. The fuel content of an aerogel material or composition can include hydrophobic organic content as well as other combustible residual alcohol solvents, filler materials, reinforcing materials, and readily hydrolyzable alkoxy groups.

[0124] Organic aerogels are generally formed from carbon-based polymer precursors. These polymer materials include, but are not limited to, resorcinol formaldehyde (RF), polyimide, polyacrylate, polymethyl methacrylate, acrylate oligomers, polyoxyalkylenes, polyurethanes, polyphenols, polybutadiene, trialkoxysilane-terminated polydimethylsiloxane, polystyrene, polyacrylonitrile, polyfurfural, melamine-formaldehyde, cresol formaldehyde, phenol-furfural, polyethers, polyols, polyisocyanates, polyhydroxybenzenes, polyvinyl alcohol dialdehydes, polycyanurates, polyacrylamides, various epoxy resins, agar, agarose, chitosan, and combinations thereof. As an example, organic RF aerogels are usually made from sol-gel polymerization of resorcinol or melamine with formaldehyde under alkaline conditions.

[0125] Organic / inorganic hybrid aerogels are primarily composed of organically modified silica ("ormosil") aerogels. These ormosil materials include an organic component covalently bonded to a silica network. Ormosils are typically formed by hydrolysis and condensation of an organically modified siloxane, R--Si(OX)3, with a conventional alkoxide precursor, Y(OX)4. In these formulas, X may represent, for example, CH3, C2H5, C3H7, C4H9; Y may represent, for example, Si, Ti, Zr, or Al; and R may be any organic fragment, such as methyl, ethyl, propyl, butyl, isopropyl, methacrylate, acrylate, vinyl, epoxide, and the like. The organic component in the ormosil aerogel may also be dispersed throughout the silica network or chemically bonded to the silica network.

[0126] In the context of the present disclosure, the term "organo-inorganic siloxane" encompasses the above materials as well as other organically modified materials, sometimes referred to as "ormocers". Organo-inorganic siloxanes are typically used as coatings, where an organo-inorganic siloxane film is cast on a substrate, for example, by a sol-gel process. Examples of other organic-inorganic hybrid aerogels of the present disclosure include, but are not limited to, silica-polyethers, silica-PMMA, silica-chitosan, carbides, nitrides, and other combinations of the above organic and inorganic aerogel-forming compounds. Published U.S. Patent Application 20050192367 (paragraphs

[0022] -

[0038] and

[0044] -

[0058] ) includes teachings of these hybrid organic-inorganic materials and is incorporated herein by reference in its entirety for each cited section and paragraph.

[0127] In certain embodiments, the aerogels of the present disclosure are inorganic silica aerogels formed primarily from prepolymerized silica precursors, preferably oligomers, or hydrolyzed silicates formed from silicon alkoxides in alcohol solvents. In certain embodiments, these prepolymerized silica precursors or hydrolyzed silicates may be formed in situ from other precursors or silicates, such as alkoxysilanes or water glass. However, the present disclosure may be practiced as a whole with any other aerogel composition known to those skilled in the art, and the present disclosure is not limited to any one precursor material or amalgam mixture of precursor materials.

[0128] As described above, the aerogel composition according to the embodiments of the present disclosure provides advantageous properties of compressibility, compression elasticity, and compliance. When used as a separator between battery cells in a battery module, the insulating sheet formed using the aerogel composition can provide resistance to compression deformation to accommodate the expansion of the battery cells caused by degradation and swelling of active materials during the battery charge / discharge cycle. During the initial assembly of the battery module, a relatively low load of 1 MPa or less is typically applied to the separator material of the battery cell, such as the enhanced aerogel composition disclosed herein. When the battery cells in the battery module expand and / or swell during the charge / discharge cycle, a load of up to about 5 MPa can be applied to the battery cell separator material, such as the enhanced aerogel composition disclosed herein. Therefore, the compressibility, compression elasticity, and compliance of the battery cell separator material are important properties.

[0129] In other embodiments, the battery thermal management component may include other heat shielding layers alone or in combination with the aerogel composition. For example, the heat shielding layer may include a material selected from the group consisting of mica, microporous silica, ceramic fiber, mineral wool, and combinations thereof. In some embodiments, the heat shielding layer may include a mica board, for example, a mica board including at least 80% mica. In some embodiments, the heat shielding layer may include an inorganic ceramic paper made of refractory ceramic fibers.

[0130] In an exemplary aspect, the present disclosure provides a thermal control member or a battery thermal management member, wherein the thermal control member or the battery thermal management member exhibits a compressibility of less than about 25% at about 25 kPa. In some embodiments, the compression force deflection at 25% deflection can be 5 to 500 kPa, or 5 to 80 kPa. The compression force deflection at 75% deflection can be 100 to 500 kPa, or 200 to 300 kPa. Optionally, when the compression is released, the thermal control member or the battery thermal management member can have sufficient elasticity to return to at least about 80%, 75%, 65%, 60% or 50% of its original thickness. In some embodiments, the thermal control member or the battery thermal management member exhibits a compressibility of less than about 25% in the range of about 25 kPa to about 35 kPa, and preferably exhibits a compressibility of less than about 50% at about 50 kPa. In some embodiments, the thermal control member or the battery thermal management member exhibits a compressibility in the range of about 25% to about 50% at about 50 kPa. In an exemplary embodiment, the thermal control member or battery thermal management member exhibits a compressibility of less than about 80% at about 245 kPa, for example, less than about 70% at about 235 kPa. In an exemplary embodiment, the thermal control member or battery thermal management member exhibits a compressibility of less than about 70% at about 345 kPa. When the thermal control member or battery thermal management member is compressed, the thermal conductivity of the thermal control member or battery thermal management member is preferably maintained at less than about 60 mW / mK, less than about 50 mW / mK, about 40 mW / mK, about 30 mW / mK, about 25 mW / mK, or a range between these values.

[0131] As discussed above, aerogel compositions according to embodiments of the present disclosure may include an aerogel framework containing macropores. Without being bound by any particular theory of operation, the presence of macropores within the aerogel framework may allow the aerogel composition, for example, to enhance compression of the aerogel composition while maintaining or even improving thermal properties, for example, reducing thermal conductivity. For example, the macropores may be deformed, crushed, or otherwise reduced in size by compressing the composition, thereby reducing the thickness of the composition under load. However, as the macropores deform, they actually become smaller pores. Therefore, as the macropores deform, the heat transfer path within the aerogel framework may be more tortuous, thereby improving thermal properties, for example, reducing thermal conductivity. In the context of the present disclosure, "mesopores" are pores with an average pore size in the range of about 2nm to about 50nm. The aerogel framework is typically mesoporous (i.e., primarily comprising pores with an average diameter in the range of about 2nm to about 50nm). In certain embodiments, the aerogel framework of the aerogel composition of the present disclosure may include macropores. In the context of the present disclosure, "macroporous" are pores with an average pore size greater than about 50nm. The aerogel framework may include both macropores and mesopores. For example, at least 10% of the pore volume of the aerogel framework may be composed of macropores, at least 5% of the pore volume of the aerogel framework may be composed of macropores, at least 75% of the pore volume of the aerogel framework may be composed of macropores, at least 95% of the pore volume of the aerogel framework may be composed of macropores, or 100% of the pore volume of the aerogel framework may be composed of macropores. In some specific embodiments, the aerogel framework may be a macroporous aerogel framework, so that most of its pore volume is composed of macropores. In some cases, the macroporous aerogel framework may also include micropores and / or mesopores. In some embodiments, the average pore size (diameter) of the pores in the aerogel framework may be greater than 50nm, greater than 50nm to 5000nm, 250nm to 2000nm, 500nm to 2000nm, 500nm to 1400nm or 1200nm. In certain embodiments, the average pore size may be greater than 50 nm in diameter, greater than 50 nm to 1000 nm, preferably 100 nm to 800 nm, more preferably 250 nm to 750 nm.

[0132] In some embodiments, the variation in pore size within the aerogel framework can be uniformly distributed throughout the aerogel framework. For example, the average pore size can be substantially the same throughout the aerogel framework.

[0133] In other embodiments, the change of pore size in the aerogel framework can be heterogeneously distributed throughout the aerogel framework. For example, the average pore size can be different in certain areas of the aerogel framework. In certain exemplary embodiments, the average pore size can be larger in the area of ​​the upper surface, the lower surface, or both the upper and lower surfaces of the aerogel framework. For example, the macropores can be distributed in the composition so that the ratio of macropores to mesopores is greater on the upper surface than on the lower surface, greater on the lower surface than on the upper surface, or greater on both the upper and lower surfaces than in the middle area between the upper and lower surfaces. For another example, the macropores can be distributed in the composition so that the ratio of macropores to mesopores is greater near the upper surface than near the lower surface, greater near the lower surface than near the upper surface, or greater near the upper and lower surfaces than in the middle area between the upper and lower surfaces. In other embodiments, in the middle area between the upper and lower surfaces of the aerogel framework, the average pore size can be larger.

[0134] The macropores can be formed during the production of the aerogel composition. For example, the formation of macropores can be induced in the gel precursor material during the transition to the gel composition. In some embodiments, the macropores can be formed by causing, for example, metastable decomposition of the gel precursor solution. For another example, the formation of macropores can be induced by adding one or more blowing agents.

[0135] The macropores present in the resulting aerogel framework may be formed by selecting processing conditions that favor the formation of macropores relative to mesopores and / or micropores. The amount of macropores can be adjusted by implementing any one, any combination, or all of the following variables: (1) polymerization solvent; (2) polymerization temperature; (3) polymer molecular weight; (4) molecular weight distribution; (5) copolymer composition; (6) amount of branching; (7) amount of crosslinking; (8) branching method; (9) crosslinking method; (10) method used to form the gel; (11) type of catalyst used to form the gel; (12) chemical composition of the catalyst used to form the gel; (13) amount of catalyst used to form the gel; (14) gel formation temperature; (15) type of gas flowing through the material during gel formation; (16) gas flow rate through the material during gel formation; (17) atmospheric pressure during gel formation; (18) removal of dissolved gases during gel formation; (19) presence of solid additives in the resin during gel formation; (20) amount of time during the gel formation process; (21) substrate used for gel formation; (22) type of solvent or solvents used in each step of the solvent exchange process; (23) the amount of solvent or solvents used in each step of the solvent exchange process (24) the composition of the one or more solvents used in each step of the solvent exchange process; (25) the residence time of the component during each step of the solvent exchange process; (26) the flow rate of the solvent exchange solvent; (27) the flow type of the solvent exchange solvent; (28) the agitation rate of the solvent exchange solvent; (29) the temperature used in each step of the solvent exchange process; (30) the ratio of the volume of the solvent exchange solvent to the volume of the component; (31) the drying method; (32) the temperature of each step of the drying method; (33) the pressure of each step of the drying method; (34) the gas composition used in each step of the drying method; (35) the gas flow rate in each step of the drying method; (36) the gas temperature during each step of the drying method; (37) the temperature of the component during each step of the drying method; (38) the presence of an enclosure around the component during each step of the drying method; (39) the type of enclosure around the component during drying; and / or (40) the solvent used in each step of the drying method. The polyfunctional amine and diamine compounds may be added separately or together in one or more portions as solids, pure substances or dissolved in a suitable solvent. In other aspects, the method of preparing an aerogel may include the following steps: (a) providing a polyfunctional amine compound and at least one diamine compound to a solvent to form a solution; (b) providing at least one dianhydride compound to the solution of step (a) under conditions sufficient to form a branched polymer matrix solution, wherein the branched polymer matrix is ​​dissolved in the solution; (c) subjecting the branched polymer matrix solution to conditions sufficient to form an aerogel having an open cell structure. The macropores present in the resulting aerogel framework may be formed in the manner described above.In one preferred and non-limiting aspect, the formation of macropores relative to smaller mesopores and micropores can be controlled primarily by controlling the polymer / solvent dynamics during gel formation.

[0136] As discussed above, aerogel compositions according to embodiments of the present disclosure may include an aerogel frame and a reinforcement material, wherein at least a portion of the reinforcement material does not include aerogel. For example, the aerogel frame may extend partially through the thickness of the reinforcement material. In these embodiments, a portion of the reinforcement material, such as OCMF, fiber, or a combination thereof, may include aerogel material, and a portion may not contain aerogel. For example, in some embodiments, the aerogel extends through about 90% of the thickness of the reinforcement material, through a range of about 50% to about 90% of the thickness of the reinforcement material, through a range of about 10% to about 50% of the thickness of the reinforcement material, or through about 10% of the thickness of the reinforcement material.

[0137] Without being bound by any particular theory of operation, an aerogel composition in which at least a portion of the reinforcement material is free of aerogel can provide advantageous properties in terms of compressibility, compression elasticity, and compliance. For example, the properties of the reinforcement material can be selected to provide sufficient reinforcement and support for thermal properties in areas containing aerogel, and also provide sufficient compressibility, compression elasticity, and / or compliance in areas without aerogel. The aerogel-containing portion of the reinforced aerogel composition can provide a desired thermal conductivity, for example, a thermal conductivity of less than about 25 mW / m*K, while the reinforcement portion without aerogel can provide or improve a desired physical property, for example, compressibility.

[0138] In certain embodiments, the method disclosed herein can be used to form an enhanced aerogel composition in which at least a portion of the reinforcing material does not contain aerogel, wherein the reinforcing material is combined with a precursor solution sufficient to partially fill the reinforcing material with a precursor solution. For example, the volume of the precursor can be less than the volume of the reinforcing material, so that the precursor only partially extends through the reinforcing body. As discussed above, when dried, the resulting enhanced aerogel composition will include an aerogel framework extending through an overall thickness less than the reinforcing material. In other embodiments, an enhanced aerogel composition in which at least a portion of the reinforcing material does not contain aerogel can be formed by removing a surface aerogel layer from the enhanced aerogel composition.

[0139] In some embodiments, a reinforcing material having a mixed property by the thickness of the reinforcing body can be used to form an enhanced aerogel composition in which at least a portion of the reinforcing material does not contain aerogel. For example, the reinforcing body can include multiple layers, and each layer has different properties, for example, the difference of average pore / chamber size, material composition, closed chamber, open chamber, surface treatment or its combination. Multiple layers can be combined to each other by flame bonding or by other suitable methods or mechanisms as discussed herein, for example, using an adhesive. The different properties of the reinforcing material can provide the different distributions of the aerogel by the layer. For example, the open chamber portion of the reinforcing material can include an aerogel frame, and the closed chamber portion remains substantially free of aerogel. Similarly, other material properties of the reinforcing material or its layer can determine the distribution of aerogel in the reinforcing body, and therefore determine the distribution of aerogel in the enhanced aerogel composition.

[0140] In some exemplary embodiments, the methods disclosed herein can be used to form a reinforced aerogel composition in which at least a portion of the reinforcement material does not contain aerogel, wherein the properties of the reinforcement material or reinforcement material layer control or influence the amount of precursor solution that fills the material or layer, for example, during the casting process, thereby providing a partial filling of the reinforcement material using the precursor solution. For example, one layer of the reinforcement can have an open chamber, while another layer of the reinforcement can have a closed chamber. When the precursor solution is combined with such a reinforcement, the gel precursor solution can penetrate into the open chamber of the layer while substantially not penetrating into the closed chamber of another layer. When drying such a composition, the resulting reinforced aerogel composition can include a portion that does not contain aerogel, for example, a closed chamber layer, while another portion, for example, an open chamber layer, contains aerogel.

[0141] In some embodiments, the additives disclosed herein (e.g., endothermic additives, light-shielding additives, fire additives, or other additives) may be unevenly distributed within the reinforced aerogel composition. For example, the additive material may change in the thickness of the aerogel composition or along the length and / or width. For example, the additive may accumulate on one side of the aerogel composition. In some embodiments, the additive material may be concentrated in a layer of an aerogel composite material, or provided as a separate layer, the separate layer consisting essentially of additives adjacent to or connected to the composite material. For example, a thermal control component or a battery thermal management component may include a layer consisting essentially of endothermic materials such as gypsum, sodium bicarbonate, and magnesium oxide-based cement. In other exemplary embodiments, the aerogel composition may further include at least one layer of other materials (in the composition or as a covering layer). For example, the layer may be a layer selected from the group consisting of a polymer sheet, a metal sheet, a fiber sheet, a highly oriented graphite material (e.g., a pyrolytic graphite sheet), and a fabric sheet. In some embodiments, the facing layer can be connected to the composition, for example, by an adhesive mechanism selected from the group consisting of: aerosol adhesives, urethane-based adhesives, acrylate adhesives, hot melt adhesives, epoxy resins, rubber resin adhesives, polyurethane composite adhesives, and combinations thereof. In some embodiments, the facing layer can be connected to the composition by a non-adhesive mechanism, for example, a mechanism selected from the group consisting of: flame gluing, needle punching, stitching, sealed bags, rivets, buttons, clamps, wrapping, brackets, and combinations thereof. In some embodiments, the facing layer can be connected to the composition using a combination of any of the above-mentioned adhesive and non-adhesive mechanisms.

[0142] As discussed herein, an aerogel composition or composite material may include a material in which aerogel particles, particles, granules, beads or powders are incorporated into a solid or semi-solid material, such as in combination with a binder, such as an adhesive, resin, cement, foam, polymer or similar solid or solidified material. For example, an aerogel composition may include a reinforcing material, aerogel particles and an optional binder. In an exemplary embodiment, a slurry containing aerogel particles and at least one type of wetting agent may be provided. For example, the aerogel particles may be coated or wetted with at least one wetting agent, such as a surfactant or a dispersant. The aerogel particles may be completely wetted, partially wetted (e.g., surface wetted) or present in the slurry. Preferred wetting agents are capable of volatilization to allow for appropriate restoration of the hydrophobicity of the hydrophobic aerogel particles. If the wetting agent is retained on the surface of the aerogel particles, the remaining wetting agent may contribute to the overall thermal conductivity of the composite material. Therefore, preferred wetting agents are removable wetting agents, such as by volatilization or other means with or without decomposition. Generally, any wetting agent compatible with aerogels may be used.

[0143] Slurries or aerogels coated with wetting agents can be used as a means of easily introducing hydrophobic aerogels into a variety of materials, such as other aqueous fluids, slurries, adhesives, binder materials, which can optionally harden to form solid materials, fibers, metallized fibers, discrete fibers, woven materials, nonwoven materials, needle-like nonwoven fabrics, cotton wool, fiber webs, mats, felts, and combinations thereof. Aerogels wetted with at least one wetting agent or slurries containing aerogels with at least one wetting agent allow for easy introduction and uniform distribution of hydrophobic aerogels. Wet laid processes, such as those described in U.S. Pat. Nos. 9,399,864, 8,021,583, 7,635,411, and 5,399,422 (each of which is incorporated herein by reference in its entirety) use aqueous slurries to spread aerogel particles, fibers, and other additives. The slurry may then be dewatered to form a layer of aerogel particles, fibers, and additives, which may be dried and optionally calendared to produce an aerogel composite.

[0144] In other embodiments, the aerogel composition may include aerogel particles, at least one inorganic matrix material, and optionally fibers, auxiliary materials, additives and other inorganic binders. In some embodiments, the inorganic matrix material may include a layered silicate, for example, a naturally occurring layered silicate such as kaolin, clay or bentonite, a synthetic layered silicate such as magadiite or kenyaite, or a mixture of these. The layered silicate may be fired or unfired, for example, to dry the material and remove water of crystallization. In some embodiments, the inorganic matrix material may also include an inorganic binder such as cement, lime, gypsum or a suitable mixture thereof combined with the layered silicate. In some embodiments, the inorganic matrix material may also include other inorganic additives disclosed herein, such as fire additives, sunscreens or combinations thereof. Exemplary methods and aerogel compositions including inorganic matrix materials are disclosed in U.S. Pat. Nos. 6,143,400, 6,083,619 (each of which is incorporated herein by reference in its entirety). In some embodiments, the aerogel composition may include aerogel particles coated on or absorbed into a textile material, a non-woven material, a needle-shaped non-woven fabric, a cotton wool, a fiber mesh, a pad, a felt, and a combination thereof. An adhesive binder may be included in the composition. Additives such as fire additives, sunscreens, or combinations thereof as disclosed herein may also be included. Exemplary methods and aerogel compositions for coating or absorbing into fabrics are disclosed in U.S. Patent Publication No. 2019 / 0264381A1 (which is incorporated herein by reference in its entirety).

[0145] As discussed herein, aerogel composites can be laminated or faced with other materials, such as reinforcement layers of facing materials. In one embodiment, the present disclosure provides a multilayer laminate comprising at least one base layer comprising a reinforced aerogel composition and at least one facing layer. In one embodiment, the facing layer comprises a reinforcing material. In one embodiment, the reinforced aerogel composition is reinforced with a fiber reinforcement layer or an open cell foam reinforcement layer. In one embodiment, the present disclosure provides a multilayer laminate comprising: a base layer comprising a reinforced aerogel composition, and at least two facing layers comprising a reinforcing material, wherein the two facing layers are on opposite surfaces of the base layer. For example, a multilayer aerogel laminate composite can be produced according to the methods and materials described in U.S. Patent Application 2007 / 0173157.

[0146] The cladding layer may include materials that will help provide specific features to the final composite structure, such as improved flexibility or reduced dust. The cladding material may be hard or flexible. The cladding material may include a conductive layer or a reflective foil. For example, the cladding material may include a metal or a metallized material. The cladding material may include a non-woven material. The cladding layer may be arranged on the surface of the composite structure or the enhanced aerogel composite material forming the composite structure (e.g., a thermal control member or a battery thermal management member). The cladding layer may form a continuous coating or bag around the composite structure or the enhanced aerogel composite material forming the composite structure (e.g., a thermal control member or a battery thermal management member). In some embodiments, one or more cladding layers may encapsulate the composite structure or the enhanced aerogel composite material forming the composite structure.

[0147] In one embodiment, the facing layer comprises a polymer sheet surrounding the composite structure; more specifically, a polymer material comprising polyester, polyethylene, polyurethane, polypropylene, polyacrylonitrile, polyamide, aramid; more specifically, a polymer such as polyethylene terephthalate, low density polyethylene, ethylene-propylene copolymer, poly(4-methylpentane), polytetrafluoroethylene, poly(1-butene), polystyrene, polyvinyl acetate, polyvinyl chloride, polyvinylidene chloride, polyvinyl fluoride, polyethylene acrylonitrile, polymethyl methacrylate, polyoxymethylene, polyphenyl sulfone, cellulose triacetate, polycarbonate, polyethylene naphthalate, polycaprolactam, polyhexamethylene adipamide, polyundecaneamide, polyimide or a combination thereof. In one embodiment, the polymer sheet comprises or consists essentially of an expanded polymer material; more specifically, an expanded polymer material comprising PTFE (ePTFE), expanded polypropylene (ePP), expanded polyethylene (ePE), expanded polystyrene (ePS) or a combination thereof. In a preferred embodiment, the facing material consists essentially of an expanded polymer material. In one embodiment, the polymer sheet comprises or consists essentially of a microporous polymer material characterized by pore sizes ranging from 0.1 μm to 210 μm, 0.1 μm to 115 μm, 0.1 μm to 15 μm, or 0.1 μm to 0.6 μm.

[0148] In one embodiment, the facing material comprises or consists essentially of a fluoropolymer material. In the context of this disclosure, the term "fluoropolymer" or "fluoropolymer material" refers to a material consisting primarily of polymerized fluorocarbons. Suitable fluoropolymer facing materials include, but are not limited to, polytetrafluoroethylene (PTFE), including microporous PTFE and expanded PTFE (ePTFE) as described in U.S. Pat. No. 5,814,405, such as (available from WLGore); polyvinyl fluoride (PVF); polyvinylidene fluoride (PVDF); perfluoroalkoxy (PFA); fluorinated ethylene-propylene (FEP); polychlorotrifluoroethylene (PCTFE); ethylene tetrafluoroethylene (ETFE); polyvinylidene fluoride (PVDF); ethylene chlorotrifluoroethylene (ECTFE); and combinations thereof. In a preferred embodiment, the facing material consists essentially of a fluoropolymer material. In a preferred embodiment, the facing material consists essentially of an expanded PTFE (ePTFE) material.

[0149] In one embodiment, the facing material comprises or consists essentially of a non-fluoropolymer material. In the context of this disclosure, the term "non-fluoropolymer" or "non-fluoropolymer material" refers to a material that does not contain a fluoropolymer material. Suitable non-fluoropolymer facing materials include, but are not limited to: aluminized polyester film; low density polyethylene, such as (available from DuPont); rubber or rubber composites; non-woven materials, elastic fibers, such as spandex, nylon, lycra or elastane; and combinations thereof. In one embodiment, the facing material is a flexible facing material.

[0150] In some embodiments, the cladding material may include automotive resins and polymers, such as those with a maximum use temperature of up to about 100C, up to about 120C, or up to about 150C. For example, the cladding material may include acrylonitrile butadiene styrene (ABS), polycarbonate ABS, polypropylene, polyurethane, polystyrene, polyethylene, polycarbonate, polyamide, PVC, or a combination thereof. For example, the aerogel composite and thermal control component or battery thermal management component according to embodiments disclosed herein may include an automotive resin or automotive polymer layer, a metal or metallized layer, and an aerogel layer.

[0151] The facing layer can be connected to the base layer by using an adhesive on the reinforcing material suitable for fixing the inorganic or organic facing material to the base layer. Examples of adhesives that can be used in the present disclosure include, but are not limited to, cement-based adhesives, sodium silicates, latex, pressure-sensitive adhesives, silicones, polystyrenes, aerosol adhesives, urethanes, acrylate adhesives, hot melt adhesive systems, adhesive systems commercially available from 3M, epoxy resins, rubber resin adhesives, polyurethane adhesive mixtures, such as those described in U.S. Patent No. 4,532,316.

[0152] The facing layer can also be connected to the base layer by using a non-adhesive material or technology suitable for fixing the inorganic or organic facing material to the reinforcing material of the base layer. Examples of non-adhesive materials or technologies that can be used in the present disclosure include, but are not limited to, heat sealing, ultrasonic stitching, RF sealing, stitching or threading, needle punching, sealed bags, rivets or buttons, clamps, wrapping or other non-adhesive laminates.

[0153] The covering layer can be connected to the base layer at any stage of production of the aerogel composite material. In one embodiment, the covering layer is connected to the base layer after the sol-gel solution is injected into the base reinforcement material, but before gelation. In another embodiment, the covering layer is connected to the base layer after the sol-gel solution is injected into the base reinforcement material and after subsequent gelation, but before aging or drying the gel material. In another embodiment, the covering layer is connected to the base layer after aging and drying the gel material. In a preferred embodiment, the covering layer is connected to the reinforcement material of the base layer before the sol-gel solution is injected into the base reinforcement material. The covering layer can be solid and impermeable to fluids. The covering layer can be porous and permeable to fluids. In a preferred embodiment, the covering layer is porous and permeable to fluids and contains holes or holes with diameters large enough to allow fluids to diffuse through the covering material. In another preferred embodiment, before the sol-gel solution is injected into the base reinforcement material, a facing layer is connected to the reinforcement material of the base layer, wherein the facing layer is porous and fluid permeable and contains pores or holes with a diameter large enough to allow the fluid to diffuse through the facing material. In another preferred embodiment, before the sol-gel solution is injected into the foam reinforcement material, a facing layer is connected to the open cell foam reinforcement material, wherein the facing layer is porous and fluid permeable and contains pores or holes with a diameter large enough to allow the fluid to diffuse through the facing material.

[0154] In some embodiments, the composite structure or the enhanced aerogel composite material forming the composite structure can be encapsulated by an encapsulation member. For example, the encapsulation member can include one or more layers of material surrounding the composite material or the composite structure and / or a material coating surrounding the composite material or the composite structure. For example, the encapsulation member can include a film, a layer, a sleeve or a coating. The encapsulation member can be made of any material suitable for surrounding the composite structure or the enhanced aerogel composite material forming the composite structure. For example, the encapsulation member can reduce or eliminate the generation of dust or particulate material that falls off from the composite structure.

[0155] The packaging member may include at least one vent that allows air to flow into and out of the panel. The packaging member may include at least one filter that filters particulate matter. In an exemplary embodiment, the packaging member includes a vent that allows air to flow into and out of the panel, and a particulate filter above the vent that retains particulate matter in the packaging member. In another embodiment, the packaging member includes an edge seal that includes at least one vent and at least one particulate filter. In other embodiments, the packaging member includes an edge seal that includes at least one vent and at least one particulate filter, wherein the vent in the edge seal allows air to flow into and out of the edge of the packaging member, and wherein the filter captures and retains particulate matter in the flowing air to prevent particulate matter from contaminating the air outside the packaging member. In some embodiments of the above aspects, the thermal control member or battery thermal management member may include multiple layers. For example, the thermal control member or battery thermal management member may include at least one layer or include a thermally conductive material, for example, a layer includes a metal, carbon, a thermally conductive polymer, or a combination thereof. As used in the context of these embodiments, a thermally conductive material refers to a material having a thermal conductivity greater than that of an aerogel composition. In certain embodiments, the thermally conductive material has a thermal conductivity at least about one order of magnitude greater than the aerogel composition. In some embodiments, the thermal control member or battery thermal management member may include multiple layers of an aerogel composition. In certain embodiments, the thermal control member or battery thermal management member may include at least one layer of thermally conductive material disposed adjacent to the aerogel composition. In certain embodiments, the thermal control member or battery thermal management member may include at least one layer of thermally conductive material disposed between at least two of the multiple layers of the aerogel composition. In some embodiments, the thermal control member or battery thermal management member may include particles of conductive material disposed within a layer of the thermal control member or battery thermal management member, for example, within a layer of an aerogel composition.

[0156] In an exemplary embodiment, the thermal control member or battery thermal management member may include a material or material layer (i.e., a heat-capacitive material) that provides heat capacity, for example, a material with a specific heat capacity of at least about 0.3 J / (gC). In some embodiments, the material that provides heat capacity has a specific heat capacity of at least about 0.5 J / (gC). For example, the material that provides heat capacity may include a metal such as aluminum, titanium, nickel, steel, iron, or a combination thereof. In some embodiments, the thermal control member or battery thermal management member may include a material layer or coating that provides heat capacity. In some embodiments, the thermal control member or battery thermal management member may include particles of a material that provides heat capacity arranged in a layer of the thermal control member or battery thermal management member, for example, a layer of an aerogel composition. In certain embodiments, the thermal control member or battery thermal management member may include at least one layer of a material that provides heat capacity disposed adjacent to the aerogel composition. In certain embodiments, the thermal control member or battery thermal management member may include at least one layer of a material that provides heat capacity disposed between at least two of the multiple layers of the aerogel composition. In an exemplary embodiment, the thermal control member or battery thermal management member may include both thermally conductive and heat-capacitive materials. For example, the thermal control member or battery thermal management member may include a material that provides both thermal capacity and thermal conductivity, for example, a metal such as aluminum, titanium, nickel, steel, iron, or a combination thereof. For another example, the thermal control member or battery thermal management member may include one or more different materials or material layers that provide thermal capacity, thermal conductivity, or a combination thereof, respectively, for example, a layer including a metal and a layer including a thermally conductive polymer.

[0157] In some embodiments, a thermally conductive paste may be used between layers of a thermal control component or a battery thermal management component to ensure uniform and consistent thermal conductivity between these layers. As used herein, thermally conductive paste refers to a variety of materials also known as thermally conductive compounds, thermally conductive greases, thermal interface materials (TIMs), thermally conductive gels, heat sinks, heat sink compounds, and thermal pastes. For example, a layer of thermally conductive paste may be disposed between the aerogel composition and any other layer, such as one or more layers including a thermally conductive or thermally capacitive material, one or more covering layers, or an encapsulating component.

[0158] As discussed herein, the thermal control member or battery thermal management member may include multiple material layers, such as a thermal insulation layer, a thermal conductive layer, a thermal capacitive layer, a thermal reflective layer, a compressible, elastic or compliant layer or a combination thereof. The combination of layers in the thermal control member or battery thermal management member may be selected to obtain the desired properties, for example, a combination of compressibility, elasticity, thermal performance, flame reaction, and other properties. In some embodiments, the thermal control member or battery thermal management member includes at least one elastic or compliant member arranged between one or more layers of thermal insulation materials (e.g., selected from mica, microporous silica, ceramic fiber, mineral wool, aerogel composition, and a combination of materials). The compliant or elastic member includes a compressible material, that is, a material that can be compressed to reduce its thickness while providing the desired compressive strength. For example, the compliant member may be a foam or other compressible material, such as a polyolefin, polyurethane, phenolic resin, melamine, cellulose acetate, or polystyrene. In certain embodiments, the thermal control or battery thermal management component may further include at least one layer of thermally conductive material or thermally capacitive material disposed between at least one compliant or elastic component and at least one layer of the multilayer reinforced aerogel composition. The thermally conductive material or thermally capacitive material may absorb and / or distribute heat within the thermal control or battery thermal management component. In some embodiments, the thermal control component or battery thermal management component may further include a heat reflective layer. For example, the heat reflective layer may include a metal foil or sheet.

[0159] In embodiments of thermal control components or battery thermal management components comprising several layers, the layers may be connected to other layers, for example, by an adhesive mechanism selected from the group consisting of aerosol adhesives, urethane-based adhesives, acrylate adhesives, hot melt adhesives, epoxy resins, rubber resin adhesives, polyurethane composite adhesives, and combinations thereof. In some embodiments, the layers may be connected by non-adhesive mechanisms, for example, a mechanism selected from the group consisting of flame gluing, needle punching, stitching, sealed bags, rivets, buttons, clamps, wrapping, brackets, and combinations thereof. In some embodiments, a combination of any of the above adhesive and non-adhesive mechanisms may be used to connect the layers together.

[0160] Figure 5 An exemplary thermal control component or battery thermal management component according to embodiments disclosed herein is shown. Figure 6As shown, an exemplary thermal control member or battery thermal management member 10 includes a thermal barrier layer 12, for example, a reinforced aerogel composition. A thermally conductive or thermally capacitive material layer 14 is arranged adjacent to the thermal barrier layer 12. The thermal control member or battery thermal management member 10 is substantially planar and has a first major outer surface defined by the outer surface of the first thermal barrier layer 12 and a second major outer surface defined by the outer surface of the thermally conductive or thermally capacitive material layer 14. In some embodiments, the thermal control member or battery thermal management member 10 includes an encapsulation member or encapsulation layer surrounding all or part of the outer surface of the thermal control member or battery thermal management member. In some embodiments, the thermal barrier layer may be surrounded by an encapsulation member or encapsulation layer surrounding all or part of the layer.

[0161] like Figure 7 As shown, an exemplary thermal control member or battery thermal management member 20 includes a first thermal protection layer 22, for example, a layer of a reinforced aerogel composition, and a second thermal protection layer 23, for example, a reinforced aerogel composition 23. A thermally conductive or thermally capacitive material layer 14 is arranged between the first thermal protection layer 22 and the second thermal protection layer 23. The thermal control member or battery thermal management member 20 is substantially planar and has a first major outer surface defined by the outer surface of the first thermal protection layer 22 and a second major outer surface defined by the outer surface of the second thermal protection layer 23. In some embodiments, the thermal control member or battery thermal management member 10 includes a packaging member or packaging layer surrounding all or part of the outer surface of the thermal control member or battery thermal management member. In some embodiments, the thermal protection layer may be surrounded by a packaging member or packaging layer surrounding all or part of the layer.

[0162] like Figure 8 As shown, an exemplary thermal control member or battery thermal management member 30 includes a first thermal protection layer 32, for example, a reinforced aerogel composition layer, and a second thermal protection layer 33, for example, a reinforced aerogel composition layer. The thermal control member or battery thermal management member 30 is substantially planar and has a first main outer surface defined by the outer surface of the first thermal protection layer 32 and a second main outer surface defined by the outer surface of the second thermal protection layer 33. A compliant material layer 34 is arranged between the first and second thermal protection layers. A first thermally conductive or thermally capacitive material layer 36 is arranged between the first thermal protection layer 32 and the compliant material layer 34. A second thermally conductive or thermally capacitive material layer 37 is arranged between the second thermal protection layer 33 and the compliant material layer 34. In some embodiments, the thermal control member or battery thermal management member 30 includes a packaging member or packaging layer surrounding all or part of the outer surface of the thermal control member or battery thermal management member. In some embodiments, each thermal protection layer may be surrounded by a packaging member or packaging layer surrounding all or part of the layer.

[0163] like Fig. 9As shown, an exemplary thermal control member or battery thermal management member 40 includes a first thermal protection layer 42, for example, a reinforced aerogel composition layer, and a second thermal protection layer 43, for example, a reinforced aerogel composition layer. The thermal control member or battery thermal management member 40 is substantially planar and has a first main outer surface defined by the outer surface of the first thermal protection layer 42 and a second main outer surface defined by the outer surface of the second thermal protection layer 43. A compliant material layer 44 is arranged between the first and second thermal protection layers. A first thermally conductive or thermally capacitive material layer 46 is arranged at the main outer surface of the first thermal protection layer 42. A second thermally conductive or thermally capacitive material layer 47 is arranged at the main outer surface of the second thermal protection layer 43. In some embodiments, the thermal control member or battery thermal management member 40 includes a packaging member or packaging layer surrounding all or part of the outer surface of the thermal control member or battery thermal management member. In some embodiments, each thermal protection layer may be surrounded by a packaging member or packaging layer surrounding all or part of the layer.

[0164] like Fig.10 As shown, an exemplary thermal control member or battery thermal management member 50 includes a first thermal protection layer 52 and at least one elastic layer 54. In some embodiments, the thermal protection layer 52 is arranged adjacent to the elastic layer 54. In some embodiments, the thermal protection layer 52 is arranged in contact with at least one elastic layer 54. For example, as disclosed in more detail herein, the thermal protection layer 52 can be connected or bonded to the elastic layer 54. In some embodiments, the thermal control member or battery thermal management member 50 includes a packaging member or packaging layer surrounding all or part of the outer surface of the battery thermal management member. In some embodiments, each thermal protection layer can be surrounded by a packaging member or packaging layer surrounding all or part of the thermal protection layer.

[0165] like Fig.11 As shown, the thermal control member or exemplary battery thermal management member 60 includes a first thermal protection layer 62, at least one elastic layer 64, and a second thermal protection layer 66. In these embodiments, the first thermal protection layer and the second thermal protection layer may be arranged on opposite sides of at least one elastic layer. In some embodiments, at least one of the thermal protection layers 62, 64 may be arranged adjacent to the elastic layer 64. In some embodiments, both thermal protection layers 62, 64 may be arranged adjacent to the elastic layer 64. In some embodiments, at least one of the thermal protection layers 62, 64 may be arranged in contact with at least one elastic layer 64. In some embodiments, both thermal protection layers 62, 64 may be arranged in contact with at least one elastic layer 64. For example, as disclosed in more detail herein, the thermal protection layer 62 may be connected or bonded to the elastic layer 54. In some embodiments, the thermal control member or battery thermal management member 50 includes a packaging member or packaging layer surrounding all or part of the outer surface of the thermal control member or battery thermal management member. In some embodiments, each thermal protection layer may be surrounded by a packaging member or packaging layer surrounding all or part of the thermal protection layer.

[0166] In an exemplary embodiment, the compressible material includes a material selected from the group consisting of: siloxane, polyolefin, polyurethane, phenolic resin, melamine, cellulose acetate and polystyrene. In an exemplary embodiment, the heat protection layer includes a material selected from the group consisting of: mica, microporous silica, ceramic fiber, mineral wool and combinations thereof. For example, at least one of the first and second heat protection layers may include a material selected from the group consisting of: mica, microporous silica, ceramic fiber, mineral wool and combinations thereof. For another example, both the first and second heat protection layers may include a material selected from the group consisting of: mica, microporous silica, ceramic fiber, mineral wool and combinations thereof.

[0167] In some embodiments, the heat shield layer comprises an aerogel composition. For example, at least one of the first and second heat shield layers may comprise an aerogel composition. For another example, both the first and second heat shield layers may comprise an aerogel composition. The aerogel of the aerogel composition may comprise an inorganic, organic, or inorganic / organic hybrid material. In an exemplary embodiment, the aerogel composition is a silica aerogel composition. The aerogel composition may comprise a reinforcing material. For example, the reinforcing material is present in the aerogel composition. In some embodiments, the reinforcing material comprises fibers. For example, the fibers may be selected from the group consisting of discrete fibers, textile materials, non-textile materials, needle-shaped non-textiles, cotton wool, mesh, mat, felt, and combinations thereof.

[0168] In any embodiment disclosed herein, the heat protection layer may have a thermal conductivity sufficient to maintain at least the surface of the elastic or compressible layer at or below the decomposition temperature of the compressible material of the elastic or compressible layer. For example, the compressible material may include one or more organic materials that decompose at high temperatures. In these embodiments, the heat protection layer may maintain at least the surface of the elastic or compressible layer at or below the decomposition temperature of at least one of the organic materials. In some embodiments, the chemical decomposition temperature of the elastic or compressible layer is greater than about 200°C. In some embodiments, the chemical decomposition temperature of the elastic or compressible layer is greater than about 240°C. In some embodiments, the chemical decomposition temperature of the elastic or compressible layer is greater than about 280°C. In some embodiments, the chemical decomposition temperature of the elastic or compressible layer is in the range of about 200°C to about 300°C. In some embodiments, the chemical decomposition temperature of the elastic or compressible layer is greater than about 300°C. In some embodiments, the chemical decomposition temperature of the elastic or compressible layer is greater than about 350°C. In some embodiments, the chemical decomposition temperature of the elastic or compressible layer is in the range of about 300°C to about 400°C.

[0169] The production of a multilayer gel or aerogel composition may include the following steps: a) connecting a fluid-permeable facing layer to a sheet of reinforcement material to produce a laminated reinforcement sheet, wherein the facing layer contains pores or holes of sufficient diameter to allow fluid to diffuse through the facing material; b) injecting a gel precursor solution into the reinforcement sheet through the facing layer; c) converting the gel precursor material into a gel material comprising a gel framework. A portion of the gel precursor solution may be retained in the pores or holes of the facing layer, so that the gel framework in the reinforcement material of the base layer will extend into at least a portion of the facing layer. The resulting product is a multilayer gel composition, which includes: a) at least one base layer comprising a reinforcement material, and a gel framework integrated into the reinforcement material; and b) at least one facing layer, which includes a fluid-permeable facing material, and a gel framework integrated into the fluid-permeable facing material; wherein at least a portion of the gel framework of the base layer extends into and is continuous with at least a portion of the gel framework of the facing layer.

[0170] Large-scale production of multilayer aerogel compositions can include a conveyor-based system, wherein production includes the following steps: a) connecting at least one fluid-permeable facing layer to a sheet of reinforcement material to produce a laminated reinforcement sheet, wherein the facing layer contains holes or pores of sufficient diameter to allow fluid to diffuse through; b) combining a gel precursor solution with the laminated reinforcement sheet at one end of the conveyor to produce a continuous reinforced gel sheet laminate; wherein at least a portion of the gel precursor solution is injected into the reinforcement sheet via the facing layer; and wherein the gel precursor solution is combined with the laminated reinforcement sheet at a rate that allows the gel precursor solution to pass through the facing layer and penetrate the reinforcement sheet. In a preferred embodiment, the reinforcement material comprises an open cell foam reinforcement material.

[0171] The reinforced, laminated gel sheet can be wound into multiple layers (preferably wound around a mandrel by uniform stretching) and processed in subsequent chemical treatment, aging and drying steps. Other spacers can be co-wound between the gel sheets to assist in the aging or drying of the gel material, such as providing a flow path for an aging agent or drying material. In a preferred embodiment, the covering layer provides a flow path for an aging agent or drying material, so that the aging and drying of the gel material does not require additional spacers.

[0172] Large-scale production of multilayer aerogel compositions can include a semi-continuous, batch-based process, which is generally referred to as a gel-in-a-roll process, wherein production includes the following steps: a) connecting a fluid-permeable facing layer to a sheet of reinforcement material, wherein the facing layer contains pores or holes of diameter large enough to allow fluid to diffuse through; b) rolling the laminate reinforcement material into multiple layers as a preform roll; and c) merging the gel precursor solution with the preform roll. Additional spacers can be co-rolled with the reinforcement material in the preform roll to provide a flow path for the gel precursor solution, aging agent, and drying material. In a preferred embodiment, the facing layer provides a flow path for the gel precursor solution, aging agent, and drying material, thereby eliminating the need for additional spacers. In a preferred embodiment, the reinforcement material includes an open cell foam reinforcement material.

[0173] Aerogel compositions according to embodiments of the present disclosure can be formed into a variety of end products. In the simplest configuration, the reinforced aerogel composition can be in sheet form. The sheet can be formed continuously or semi-continuously, for example, as a rolled product, or can be cut into sheets of a desired size and shape, or otherwise formed from larger sheets. The sheet material can be used to form a thermal barrier between battery cells. In other configurations, the reinforced aerogel composition can be formed into a bag, for example, to contain a soft pack battery of a battery, or formed into a cylinder to contain a cylindrical battery cell.

[0174] Aerogel composites of the present disclosure can be formed into a range of three-dimensional forms, including panels, pipe preforms, half shell preforms, elbows, joints, bags, cylinders, and other shapes commonly required for the application of insulating materials in industrial and commercial applications. In one embodiment, the reinforcing material is formed into a desired shape before injecting the gel precursor material. The gel material is processed in a manner that allows the preform to retain its shape, thereby producing a reinforced aerogel preform having a desired shape. Due to the difficulties faced in processing gel materials having a variety of shapes and configurations, such techniques for forming shaped aerogel preforms can be difficult and inefficient.

[0175] In an exemplary embodiment of the present disclosure, an aerogel can be formed by a gel precursor or a combination of gel precursors comprising at least one hydrophobic group. These aerogels, for example, inorganic aerogels, such as silica-based aerogels can include hydrophobically bonded silicon. For example, the source of the hydrophobically bonded silicon in the aerogel can be one or more hydrophobic precursor materials. In an embodiment of the present disclosure, the aerogel formed by these precursors can be hydrophobic. In some embodiments, the aerogel formed by these precursors can be hydrophobic in nature.

[0176] In the context of the present disclosure, the term "essentially hydrophobic" refers to a material that is not modified by a hydrophobic agent and has hydrophobicity. For example, an aerogel can be treated to impart or improve hydrophobicity. The hydrophobic treatment can be applied to a sol-gel solution, a wet gel before liquid phase extraction, or an aerogel after liquid phase extraction. The hydrophobic treatment is performed by reacting the hydroxyl moieties on the gel, such as the silanol groups (Si-OH) present on the silica gel framework with the functional groups of the hydrophobic agent. The resulting reaction converts the silanol groups and the hydrophobic agent into hydrophobic groups on the silica gel framework. The hydrophobic agent compound can react with the hydroxyl groups on the gel according to the following reaction: R N MX 4-N (Hydrophobic agent) + MOH (Silanol) → MOMR N (hydrophobic group) + HX. The hydrophobic treatment can be performed on the external macroscopic surface of the silica gel or on the internal pore surface within the porous network of the gel. Published U.S. Patent Application 2016 / 0096949A1 (paragraphs

[0044] -

[0048] ) teaches hydrophobic treatment, and the patent application is incorporated herein by reference according to the various cited paragraphs. However, as discussed above, aerogels according to embodiments of the present disclosure are hydrophobic and have not been treated for hydrophobicity, for example, without a hydrophobic agent.

[0177] The production of aerogels generally includes the following steps: i) forming a sol-gel solution; ii) forming a gel from the sol-gel solution; iii) extracting the solvent from the gel material by innovative processing and extraction to obtain a dry aerogel material. This method will be discussed in more detail below, specifically in the context of forming inorganic aerogels, such as silica aerogels. However, the specific examples and descriptions provided herein are not intended to limit the present disclosure to any specific type of aerogel and / or preparation method. Unless otherwise stated, the present disclosure may include any aerogel formed by any relevant preparation method known to those skilled in the art.

[0178] The first step in forming an inorganic aerogel is typically to form a sol-gel solution by hydrolysis and condensation of a silica precursor, such as, but not limited to, a metal alkoxide precursor in an alcohol-based solvent. The major variables in forming an inorganic aerogel include the type of alkoxide precursor included in the sol-gel solution, the nature of the solvent, the processing temperature and pH of the sol-gel solution (which can be changed by adding acid or base), and the ratio of precursor / solvent / water in the sol-gel solution. Controlling these variables in forming the sol-gel solution can allow control of the growth and aggregation of the gel framework during the subsequent transition of the gel material from the "sol" state to the "gel" state. Although the properties of the aerogel produced are affected by the pH of the precursor solution and the molar ratio of the reactants, any pH and any molar ratio that allows the formation of a gel can be used in the present disclosure.

[0179] The sol-gel solution is formed by mixing at least one gelling precursor with a solvent. Suitable solvents for forming the sol-gel solution include lower alcohols having 1 to 6 carbon atoms, specifically lower alcohols having 2 to 4 carbon atoms, although other solvents known to those skilled in the art can be used. Examples of useful solvents include, but are not limited to, methanol, ethanol, isopropanol, ethyl acetate, ethyl acetoacetate, acetone, methylene chloride, tetrahydrofuran, and the like. A variety of solvents can also be combined to achieve a desired dispersion level or to optimize the performance of the gel material. Therefore, the selection of the optimal solvent for the sol-gel and gel forming steps depends on the specific precursors, fillers, and additives incorporated into the sol-gel solution; as well as the target processing conditions for gelling and liquid extraction and the desired properties of the final aerogel material.

[0180] Water may also be present in the precursor-solvent solution. Water acts to hydrolyze the metal alkoxide precursor into a metal hydroxide precursor. The hydrolysis reaction may be (for example, using TEOS in an ethanol solvent): Si(OC2H5)4+4H2O→Si(OH)4+4(C2H5OH). The resulting hydrolyzed metal hydroxide precursor is still suspended in the solvent solution in a "sol" state, either as a single molecule or as a small polymeric (or oligomeric) colloidal molecule cluster. For example, the polymerization / condensation of the Si(OH)4 precursor may occur as follows: 2Si(OH)4=(OH)3Si-O-Si(OH)3+H2O. This polymerization reaction may continue until a colloidal cluster of polymeric (or oligomeric) SiO2 (silicon dioxide) molecules is formed.

[0181] Acids and bases can be incorporated into the sol-gel solution to control the pH of the solution and catalyze the hydrolysis and condensation reactions of the precursor materials. Although any acid can be used to catalyze the precursor reaction and obtain a lower pH solution, exemplary acids include: HCl, H2SO4, H3PO4, oxalic acid, and acetic acid. Similarly, any base can be used to catalyze the precursor reaction and obtain a high pH solution, wherein exemplary bases include NH4OH.

[0182] Strong base can be used for catalytic precursor reaction and obtain high pH solution. Using strong base to catalyze precursor reaction can make the content of hydrophobic inorganic precursor material (such as MTES or DMDES) significantly higher than the possible content using weak base (such as including NH4OH base). In the context of the present disclosure, term "strong base" refers to both inorganic base and organic base. For example, the strong base according to the embodiment of this paper includes the cation selected from the group consisting of lithium, calcium, sodium, potassium, rubidium, barium, strontium and guanidinium. For another example, the base catalyst for catalytic precursor reaction can include catalytic amount of sodium hydroxide, lithium hydroxide, calcium hydroxide, potassium hydroxide, strontium hydroxide, barium hydroxide, guanidine hydroxide, sodium hydroxide, tetrabutylammonium hydroxide, tetramethylammonium hydroxide, choline hydroxide, phosphonium hydroxide, DABCO, DBU, guanidine derivatives, amidine or phosphazene.

[0183] The sol-gel solution may include other co-gelling precursors, as well as filler materials and other additives. The filler materials and other additives may be dispersed into the sol-gel solution at any time point before or during the formation of the gel. The filler materials and other additives may also be incorporated into the gel material after gelation by a variety of techniques known to those skilled in the art. In some embodiments, the sol-gel solution including gelling precursors, solvents, catalysts, water, filler materials and other additives is a uniform solution that can effectively form a gel under suitable conditions.

[0184] Once the sol-gel solution is formed and optimized, the gel-forming components in the sol-gel can be converted into a gel material. The method of converting the components forming the gel into a gel material includes an initial gel formation step, wherein the gel solidifies until the gel point of the gel material. The gel point of the gel material can be regarded as the point where the gel solution exhibits resistance to flow and / or forms a substantially continuous polymer framework throughout its volume. A range of gel formation techniques are known to those skilled in the art. Examples include, but are not limited to, maintaining the mixture in a static state for a sufficient period of time; adjusting the pH of the solution; adjusting the temperature of the solution; directing energy forms to the mixture (ultraviolet, visible light, infrared, microwave, ultrasound, particle radiation, electromagnetic); or a combination thereof.

[0185] The method of converting the components (gel precursors) of the gel forming into the gel material may also include an aging step (also referred to as curing) before extracting the liquid or removing the solvent (also referred to as gel drying) from the gel. After it reaches its gel point, aging the gel material can further strengthen the gel framework by increasing the number of crosslinks in the network. The duration of gel aging can be adjusted to control various properties within the aerogel material produced. The aging process can be useful in preventing potential volume loss and shrinkage during liquid extraction. Aging can include maintaining the gel (before extraction) in a static state for an extended period of time, maintaining the gel at an elevated temperature, adding a compound that promotes crosslinking, or any combination thereof. The preferred aging temperature is generally between about 10°C and about 100°C, although other suitable temperatures are also contemplated herein. Aging of the gel material generally continues until liquid extraction of the wet gel material.

[0186] The time period for converting a gel-forming material (gel precursor) to a gel material includes the duration of initial gel formation (from the start of gelation until the gel point), and the duration of any subsequent solidification and aging of the gel material (also referred to as gel drying) prior to liquid extraction or removal of solvent from the gel (from the gel point to the start of liquid extraction / removal of solvent). The total time period for converting a gel-forming material to a gel material is typically from about 1 minute to several days, typically about 30 hours or less, about 24 hours or less, about 15 hours or less, about 10 hours or less, about 6 hours or less, about 4 hours or less, about 2 hours or less, and preferably, about 1 hour or less, about 30 minutes or less, about 15 minutes or less, or about 10 minutes or less.

[0187] In another embodiment, the produced gel material can be washed in a suitable second solvent to replace the main reaction solvent present in the wet gel. These second solvents can be straight chain monohydric alcohols with one or more aliphatic carbon atoms, dihydric alcohols with two or more carbon atoms, branched alcohols, cyclic alcohols, alicyclic alcohols, aromatic alcohols, polyols, ethers, ketones, cyclic ethers or their derivatives. In another embodiment, the produced gel material can be washed in an additional amount of the same solvent present in the gel material, which can, among other things, remove any undesirable byproducts or other precipitates in the gel material.

[0188] Once the gel material is formed and processed, the liquid of the gel can then be at least partially extracted from the wet gel using extraction methods including innovative processing and extraction techniques to form an aerogel material. Liquid extraction plays an important role in engineering aerogel properties such as porosity and density and related properties such as thermal conductivity, among other factors. Generally, an aerogel is obtained when the liquid is extracted from the gel in a manner that results in low shrinkage of the porous network and framework of the wet gel. This liquid extraction may also be referred to as solvent removal or drying, etc.

[0189] An example of an alternative method for forming a silica aerogel uses a metal oxide salt, such as sodium silicate, also known as water glass. First, a silicic acid precursor solution is formed by mixing sodium silicate with water and an acid to produce a water glass solution. Salt byproducts can be removed from the silicic acid precursor by ion exchange, surfactant separation, membrane filtration or other chemical or physical separation techniques. The resulting sol can then be gelled, such as by adding an alkaline catalyst, to produce a hydrogel. The hydrogel can be washed to remove any residual salts or reactants. The operation of removing water from the gel pores can then be implemented by exchanging with a polar organic solvent (such as ethanol, methanol or acetone). The liquid in the gel is then at least partially extracted using innovative processing and extraction techniques.

[0190] Aerogels are usually formed by removing a liquid mobile phase from a gel material at a temperature and pressure close to or above the critical point of the liquid mobile phase. Once the critical point (near critical) or the critical point (supercritical) is reached (i.e., the pressure and temperature of the system are at or above the critical pressure and critical temperature, respectively), a new supercritical phase different from the liquid or vapor phase appears in the fluid. Then, the solvent can be removed without introducing a liquid-gas interface, capillary pressure, or any related mass transfer limitations usually associated with the liquid-gas boundary. In addition, the supercritical phase is usually more miscible with organic solvents and therefore has better extraction capabilities. Co-solvents and solvent exchange are also commonly used to optimize supercritical fluid drying processes.

[0191] If evaporation or extraction occurs just below the critical point, the capillary forces generated by the evaporation of the liquid can cause shrinkage and pore collapse within the gel material. Maintaining the mobile phase near or above the critical pressure and temperature during the solvent extraction process will reduce the negative effects of these capillary forces. In certain embodiments of the present disclosure, the use of near-critical conditions just below the critical point of the solvent system can allow the production of aerogel materials or compositions with sufficiently low shrinkage, thereby producing commercially viable finished products.

[0192] Several other aerogel extraction techniques are known in the art, including a range of different methods using supercritical fluids in drying aerogels. For example, Kistler (J. Phys. Chem. (1932) 36: 52-64) describes a simple supercritical extraction method in which the gel solvent is maintained above its critical pressure and temperature, thereby reducing evaporative capillary forces and maintaining the structural integrity of the gel network. U.S. Patent No. 4,610,863 describes an extraction method in which the gel solvent is exchanged with liquid carbon dioxide and then extracted under conditions in which the carbon dioxide is in a supercritical state. U.S. Patent No. 6670402 teaches the production of aerogels by extracting liquid from a gel by rapid solvent exchange by injecting supercritical (rather than liquid) carbon dioxide into an extractor that has been preheated and pre-pressurized to substantially supercritical conditions or above supercritical conditions. U.S. Patent No. 5962539 describes a method for obtaining aerogels from polymer materials in sol-gel form in an organic solvent by exchanging the organic solvent for a fluid having a critical temperature below the polymer decomposition temperature and extracting the fluid / sol-gel using a supercritical fluid (such as supercritical carbon dioxide, supercritical ethanol or supercritical hexane). U.S. Patent No. 6315971 discloses a method for producing a gel composition, the method comprising drying a wet gel comprising gel solids and a desiccant, thereby removing the desiccant under drying conditions sufficient to reduce gel shrinkage during drying. U.S. Patent No. 5420168 describes a method for making resorcinol / formaldehyde aerogels using a simple air drying method. U.S. Patent No. 5565142 describes a drying technique in which the gel surface is modified to be stronger and more hydrophobic so that the gel framework and pores can resist collapse during ambient drying or subcritical extraction. Other examples of extracting liquids from aerogel materials can be found in U.S. Patent Nos. 5275796 and 5395805. U.S. Patent Publication No. 2019 / 0161909 provides an example of a method for producing high-density aerogels using alkoxysilanes and water glass.

[0193] One embodiment of extracting liquid from a wet gel uses a supercritical fluid (such as carbon dioxide), which includes, for example, first substantially exchanging the primary solvent (primary solvent) present in the pore network of the gel with liquid carbon dioxide; and then heating the wet gel (usually in an autoclave) to a temperature exceeding the critical temperature of carbon dioxide (about 31.06°C) and raising the system pressure to a pressure greater than the critical pressure of carbon dioxide (about 1070 psig). The pressure around the gel material can fluctuate slightly to facilitate the removal of liquid from the gel. The carbon dioxide can be recycled through the extraction system to facilitate the continuous removal of the primary solvent from the wet gel. Finally, the temperature and pressure are slowly returned to ambient conditions to produce a dry aerogel material. The carbon dioxide can also be pretreated to a supercritical state before injection into the extraction chamber.

[0194] Another example of an alternative method for forming aerogels involves chemically modifying the matrix material in its wet gel state by converting surface hydroxyl groups to hydrophobic trimethylsilyl ethers, thereby reducing the destructive capillary pressure at the solvent / pore interface, thereby allowing liquid to be extracted from the gel material at temperatures and pressures below the critical point of the solvent.

[0195] In another embodiment, the liquid (solvent) in the gel material can be frozen at a relatively low temperature and then subjected to a sublimation process to remove the solvent from the gel material. Such removal or drying of the solvent from the gel material is understood to be within the scope of the present disclosure. These removals substantially retain the gel structure, thereby producing an aerogel with unique properties.

[0196] Large-scale production of aerogel materials or compositions can be complicated by difficulties associated with large-scale continuous formation of gel materials; and difficulties associated with large-scale extraction of liquids from gel materials using innovative processing and extraction techniques. In certain embodiments, the aerogel materials or compositions of the present disclosure are suitable for large-scale production. In certain embodiments, the gel materials of the present disclosure can be large-scale produced by continuous casting and gelation methods. In certain embodiments, large-scale production of aerogel materials or compositions of the present disclosure requires the use of large-scale extraction vessels. Large-scale extraction vessels of the present disclosure may include extraction vessels having the following volumes: about 0.1 m 3 or larger, about 0.25m 3 or larger, about 0.5m 3 or larger or about 0.75m 3 or larger.

[0197] The aerogel compositions of the present disclosure may have a thickness of 15 mm or less, 10 mm or less, 5 mm or less, 4 mm or less, 3 mm or less, 2 mm or less, 1 mm or less, 0.5 mm or less, 0.3 mm or less, or a thickness range between any combination of the foregoing thicknesses.

[0198] Aerogel compositions can be reinforced with a variety of reinforcing materials to achieve a more flexible, elastic and compliant composite product. Reinforcing materials can be added to the gel at any point in the gelling process to produce a wet reinforced gel composition. The wet gel composition can then be dried to produce a reinforced aerogel composition.

[0199] Aerogel compositions can be reinforced with a variety of open cell macroporous framework reinforcement materials OCMF to achieve more flexible, elastic and compliant composite products. OCMF reinforcements can be added to the gel at any time point in the gelation process before gelation to produce a wet reinforced gel composition. The wet gel composition can then be dried to produce an OCMF-reinforced aerogel composition. The OCMF reinforcements can be formed from an organic polymer material (such as melamine or a melamine derivative) and are present in the form of a continuous sheet or plate.

[0200] Melamine OCMF materials can be produced from melamine-formaldehyde precondensate solutions. The aqueous solution of melamine-formaldehyde condensation products is produced by mixing melamine-formaldehyde precondensate with solvent, emulsifier / dispersant, curing agent (such as acid) and blowing agent (such as C5 to C7 hydrocarbon). Then, the melamine-formaldehyde solution or resin is cured at a high temperature higher than the boiling point of the blowing agent to produce an OCMF comprising a plurality of interconnected three-dimensional branched melamine structures, wherein the corresponding interconnected pore network is integrated in the framework. The molar ratio of formaldehyde to melamine of the melamine-formaldehyde precondensate is generally in the range of 5:1 to 1.3:1, and generally in the range of 3.5:1 to 1.5:1. The precondensate can be in the form of a powder, spray, resin or solution. The solvent contained in the melamine-formaldehyde precondensate solution can include an alcohol, such as methanol, ethanol or butanol.

[0201] The emulsifier / dispersant contained in the melamine-formaldehyde precondensation solution may include anionic surfactants, cationic emulsifiers or nonionic surfactants. Useful anionic surfactants include, but are not limited to, diphenylene oxide sulfonates, alkanes and alkylbenzene sulfonates, alkylnaphthalene sulfonates, olefin sulfonates, alkyl ether sulfonates, fatty alcohol sulfates, ether sulfates, α-sulfo fatty acid esters, acylaminoalkane sulfonates, acylhydroxyethyl sulfonates, alkyl ether carboxylates, N-acyl sarcosinates, alkyl and alkyl ether phosphates. Useful cationic emulsifiers include, but are not limited to, alkyl triammonium salts, alkylbenzyl dimethyl ammonium salts or alkyl pyridinium salts. Useful nonionic surfactants include, but are not limited to, alkylphenol polyglycol ethers, fatty alcohol polyglycol ethers, fatty acid polyglycol ethers, fatty acid alkanolamides, ethylene oxide-propylene oxide block copolymers, amine oxides, glycerol fatty acid esters, dehydrated sorbitan esters and alkyl polyglycosides. Emulsifiers / dispersants may be added in an amount of 0.2 to 5% by weight, based on the melamine-formaldehyde precondensate.

[0202] The curing agent contained in the melamine-formaldehyde precondensate solution may include an acidic compound. The amount of these curing agents is generally in the range of 0.01% to 20% by weight, and generally in the range of 0.05% to 5% by weight, all based on the melamine-formaldehyde precondensate. Useful acidic compounds include, but are not limited to, organic and inorganic acids, for example, selected from the group consisting of hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, formic acid, acetic acid, oxalic acid, toluenesulfonic acid, aminosulfonic acid, anhydrides and mixtures thereof.

[0203] The blowing agent contained in the melamine-formaldehyde precondensation solution may include a physical blowing agent or a chemical blowing agent. Useful physical blowing agents include, but are not limited to, hydrocarbons such as pentane and hexane; halogenated hydrocarbons, more specifically chlorinated and / or fluorinated hydrocarbons, such as dichloromethane, chloroform, trichloroethane, chlorofluorocarbons and hydrochlorofluorocarbons (HCFCs); alcohols such as methanol, ethanol, n-propanol or isopropanol; ethers, ketones and esters such as methyl formate, ethyl formate, methyl acetate or ethyl acetate; and gases such as air, nitrogen or carbon dioxide. In certain embodiments, a physical blowing agent having a boiling point between 0°C and 80°C is preferably added. Useful chemical blowing agents include, but are not limited to, isocyanates mixed with water (thereby releasing carbon dioxide as an active blowing agent); carbonates and / or bicarbonates mixed with acids (releasing carbon dioxide as an active blowing agent); and azo compounds such as azodicarbonamide. The blowing agent is present in the melamine-formaldehyde precondensate solution in an amount of 0.5 to 60% by weight, specifically 1 to 40% by weight, and in certain embodiments 1.5 to 30% by weight.

[0204] The melamine-formaldehyde precondensation solution can be formed into a melamine OCMF material by heating the solution to a temperature generally above the boiling point of the blowing agent used, thereby forming an OCMF comprising a plurality of interconnected three-dimensional branched melamine structures, wherein a corresponding network of interconnected open cells is integrated into the framework. The introduction of thermal energy can be achieved by electromagnetic radiation, for example, by high frequency radiation of 5 to 400 kW per kg of the mixture, for example 5 to 200 kW, and in certain embodiments 9 to 120 kW, used in the frequency range of 0.2 to 100 GHz or more specifically 0.5 to 10 GHz. A magnetron is a useful source of dielectric radiation, and one magnetron can be used, or two or more magnetrons can be used simultaneously.

[0205] The OCMF material may be dried to remove residual liquid (water, solvent, blowing agent) from the OCMF material. A post-treatment may also be used to hydrophobize the OCMF material. Such a post-treatment may use a hydrophobic coating agent with high thermal stability and / or low flammability, such as silicones, silicates, or fluorinated compounds.

[0206] The density of the melamine OCMF is typically in the range of 0.005 to 0.3 g / cc, such as in the range of 0.01 to 0.2 g / cc, in certain embodiments in the range of 0.03 to 0.15 g / cc, or most specifically in the range of 0.05 to 0.15 g / cc. The average pore size of the melamine OCMF is typically in the range of 10 μm to about 1000 μm, specifically in the range of 50 to 700 μm.

[0207] In one embodiment, the OCMF reinforcement material is introduced into the aerogel composition as a continuous sheet. The method includes first producing a continuous OCMF reinforced gel sheet by pouring or dipping a gel precursor solution into a continuous OCMF reinforcement material sheet, and forming the material into a reinforced gel composite sheet. Then, the liquid can be at least partially extracted from the OCMF reinforced gel composite sheet to produce a sheet-like OCMF reinforced aerogel composition.

[0208] Aerogel compositions can include sunscreens to reduce the radiation component of heat transfer. At any time point before gel formation, sunscreen compounds or their precursors can be dispersed in a mixture containing a gel precursor. Examples of sunscreen compounds include, but are not limited to, boron carbide (B4C), diatomaceous earth, manganese ferrite, MnO, NiO, SnO, Ag2O, Bi2O3, carbon black, graphite, titanium oxide, iron titanium oxide, aluminum oxide, zirconium silicate, zirconium oxide, iron (II) oxide, iron (III) oxide, manganese dioxide, iron titanium oxide (ilmenite), chromium oxide, carbide (such as SiC, TiC or WC) or a mixture thereof. Examples of sunscreen compound precursors include, but are not limited to, TiOSO4 or TiOCl2. In some embodiments, the sunscreen compound used as an additive may not include whiskers or fibers of silicon carbide. When the aerogel composition is intended for use in electronic devices, for example, in batteries as a barrier layer or other related applications, the composition including the sunscreen may desirably have high dielectric strength and high volume and surface resistivity. In these embodiments, the carbon additive used as a sunscreen can be non-conductive or modified to reduce conductivity. For example, the sunscreen can be surface oxidized to reduce conductivity. In some embodiments, carbon-containing additives with inherent conductivity can be used as sunscreens in aerogel compositions intended for use in electronic devices. In these embodiments, conductive carbon-containing additives can be used at concentrations below the percolation threshold to provide compositions with suitable dielectric strength for electronic devices.

[0209] The aerogel composition may include one or more pyrotechnic additives. In the context of the present disclosure, the term "pyrotechnic additive" refers to a material that has an endothermic effect when reacting with fire and can be incorporated into the aerogel composition. In addition, in certain embodiments, the endothermic decomposition (ED ) has a starting temperature greater than the thermal decomposition temperature (T d ) has a starting temperature no higher than 100°C, and in certain embodiments, E D The T of the aerogel composition in which the fire-type additive is present is also d The lowest temperature is no more than 50℃. In other words, the E D The range is (T d -50℃) to (T d +100℃):

[0210]

[0211] The pyrotechnic additive may be mixed or otherwise dispersed into a medium comprising ethanol and optionally up to 10% vol. water prior to, simultaneously with, or even after incorporation into or mixing with a sol (e.g., a silica sol prepared from an alkyl silicate or water glass in a variety of ways as understood in the art). The mixture may be mixed and / or stirred as desired to achieve a substantially uniform dispersion of the additive in the medium. Without being bound by theory, the use of hydrated forms of the above-described clays and other pyrotechnic additives provides additional endothermic effects. For example, halloysite clay (commercially available from Applied Minerals, Inc. under the trade name DRAGONITE or commercially available from Imerys simply as Halloysite), kaolinite clay is an aluminum silicate clay whose hydrated form has an endothermic effect (gas dilution) by releasing water of hydration at elevated temperatures. As another example, hydrated forms of carbonates may release carbon dioxide upon heating or elevated temperatures.

[0212] In the context of the present disclosure, the term "heat of dehydration" refers to the amount of heat required to evaporate water (and, if applicable, dihydroxylate) from a material in a hydrated form when not exposed to elevated temperatures. The heat of dehydration is usually expressed on a unit weight basis.

[0213] In certain embodiments, the fire additive of the present disclosure has a thermal decomposition onset temperature of about 100°C or more, about 130°C or more, about 200°C or more, about 230°C or more, about 240°C or more, about 330°C or more, 350°C or more, about 400°C or more, about 415°C or more, about 425°C or more, about 450°C or more, about 500°C or more, about 550°C or more, about 600°C or more, about 650°C or more, about 700°C or more, about 750°C or more, about 800°C or more, or in a range between any two of these values. In certain embodiments, the fire additive of the present disclosure has a thermal decomposition onset temperature of about 440°C or 570°C. In certain embodiments, the fire additive of the present disclosure has a T of 100°C or more than that of the aerogel composition (without the fire additive) into which the fire additive is incorporated. d The thermal decomposition starting temperature is no more than 50°C, no more than 40°C, no more than 30°C, no more than 20°C, no more than 10°C, no more than 5°C, or in the range between any two of these values.

[0214] The pyrotechnic additives of the present disclosure include clay materials such as, but not limited to, layered silicate clays (e.g., illite), kaolin or kaolinite (aluminum silicate; Al2Si2O5(OH)4), metakaolinite, halloysite (aluminum silicate; Al2Si2O5(OH)4), andelite (aluminum silicate; Al2Si2O5(OH)4), mica (silicon oxide mineral), diaspore (aluminum hydroxide; α-AlO(OH)), gibbsite (aluminum hydroxide), boehmite (aluminum hydroxide; γ-AlO(OH)), montmorillonite, beidenite, pyrophyllite (aluminum silicate; Al2Si4O 10(OH)2), nontronite, mica, bentonite, vermiculite, rectorite, green scale stone, attapulgite, green opal, volcanic ridgestone, hydroalphinite, iron beidellite, fluorite, holmite, blue kaolinite, micro-kaolin, hydrotalcite and alunite, sodium bicarbonate (NaHCO3), magnesium hydroxide (or magnesium dihydroxide, "MDH"), alumina trihydrate ("ATH"), gypsum (calcium sulfate dihydrate; CaSO4·2H2O), hydrocarbonite (MgCO3·2H2O), nesquehonite (MgCO3·3H2O), pentahydrate magnesite (MgCO3·5H2O), hydromagnesite (hydrated magnesium carbonate; Mg5(CO3)4(OH)2·4H2O), other carbonates, such as but not limited to dolomite and lithium carbonate. Among the clay materials, certain embodiments of the present disclosure use clay materials having at least a partial layered structure. In certain embodiments of the present disclosure, the clay material as a fire additive in the aerogel composition has at least some water, such as water in a hydrated form. The additive may be in a hydrated crystalline form or may be hydrated in the production / processing of the composition of the present disclosure. In certain embodiments, the fire additive also includes a low melting point additive that absorbs heat without changing the chemical composition. Examples of this type are low melting point glasses, such as inert glass beads. Other additives that may be useful in the composition of the present disclosure include, but are not limited to, wollastonite (calcium silicate) and titanium dioxide (TiO2). In certain embodiments, other additives may include infrared sunscreens, such as, but not limited to, titanium dioxide or silicon carbide, ceramifiers, such as, but not limited to, low melting point glass powder, calcium silicate or carbonizers, such as, but not limited to, phosphates and sulfates. In certain embodiments, additives may require special processing considerations, such as techniques to ensure that the additives are evenly distributed and do not clump severely and cause product performance changes. Processing techniques may include other static and dynamic mixers, stabilizers, adjustment of process conditions, and other techniques known in the art.

[0215] The amount of additives in the aerogel compositions disclosed herein may depend on the desired properties of the composition. The amount of additives used in the preparation and processing of the sol-gel composition generally refers to the weight percentage relative to the silica content in the sol. Relative to the silica content, the amount of additives in the sol may vary between about 5wt% to about 70wt% by weight. In certain embodiments, the amount of additives in the sol is between 10wt% and 60wt% relative to the silica content, and in certain preferred embodiments, it is between 20wt% and 40wt% relative to the silica content. In an exemplary embodiment, the amount of additives in the sol relative to the silica content is in the range of about 5% to about 20%, about 10% to about 20%, about 10% to about 30%, about 10% to about 20%, about 30wt% to about 50wt%, about 35wt% to about 45wt% or about 35wt% to about 40wt% relative to the silica content. In certain embodiments, the amount of the additive in the sol is at least about 10wt% relative to the silica content or about 10wt% relative to the silica content. In certain embodiments, the amount of the additive is in the range of about 5wt% to about 15wt% relative to the silica content. In certain embodiments, the additive can be more than one type. One or more fire additives may also be present in the final aerogel composition. In some preferred embodiments including aluminum silicate fire additives, the additive is present in the aerogel composition at about 60-70wt% relative to the silica content. For example, in some preferred embodiments including aluminum silicate fire additives, such as kaolin, or aluminum silicate fire additives, such as kaolin and alumina trihydrate ("ATH"), the total amount of additives present in the aerogel composition is about 30-40wt% relative to the silica content. For another example, in some preferred embodiments in which the additive includes silicon carbide, the total amount of additives present in the aerogel composition is about 30-40wt% relative to the silica content, for example, 35wt%. For another example, in some preferred embodiments where the additive includes silicon carbide, the total amount of the additive present in the aerogel composition is about 5-15 wt %, eg, 10 wt %, relative to the silica content.

[0216] When referring to the final reinforced aerogel composition, the amount of additives generally refers to the weight percentage of the final reinforced aerogel composition. The amount of additives in the final reinforced aerogel composition can be changed between about 1% to about 50%, about 1% to about 25%, or about 10% to about 25% by weight of the reinforced aerogel composition. In an exemplary embodiment, the amount of additives in the final reinforced aerogel composition is in the range of about 10% to about 20% by weight of the reinforced aerogel composition. In an exemplary embodiment, the amount of additives in the final reinforced aerogel composition as a percentage of the weight of the composition is about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20% or in the range between any of the above percentages. In certain embodiments, the amount of additives in the final reinforced aerogel composition is about 15% by weight of the reinforced aerogel composition. In certain embodiments, the amount of additive in the final reinforced aerogel composition is about 13% by weight of the reinforced aerogel composition. For example, in some preferred embodiments including additives such as silicon carbide, the total amount of additive present in the aerogel composition is about 10-20% by weight of the reinforced aerogel composition, for example, about 15%. For another example, in some preferred embodiments where the additive includes silicon carbide, the total amount of additive present in the aerogel composition is about 3-5% by weight of the reinforced aerogel composition, for example, about 4%.

[0217] In certain embodiments, fire additives can be classified or grouped based on their thermal decomposition starting temperatures. For example, fire additives can be classified or grouped as having a thermal decomposition starting temperature of less than about 200°C, less than about 400°C, or greater than about 400°C. For example, additives having a thermal decomposition starting temperature of less than about 200°C include sodium bicarbonate (NaHCO3), magnesite (MgCO3·3H2O), and gypsum (calcium sulfate dihydrate; CaSO4·2H2O). For another example, additives having a thermal decomposition starting temperature of less than about 400°C include alumina trihydrate ("ATH"), hydromagnesite (hydrated magnesium carbonate; Mg5(CO3)4(OH)2·4H2O), and magnesium hydroxide (or magnesium dihydroxide; "MDH"). For another example, the additive having a thermal decomposition onset temperature less than about 400°C includes halloysite (aluminum silicate; Al2Si2O5(OH)4), kaolin or kaolinite (aluminum silicate; Al2Si2O5(OH)4), boehmite (aluminum oxide hydroxide; γ-AlO(OH)), or a high temperature phase change material (PCM).

[0218] In certain embodiments of the present disclosure, clay materials, for example, aluminosilicate clays, such as halloysite or kaolinite, are dehydrated forms as additives in aerogel compositions, for example, meta-haloysite or metakaolin. Other additives that may be useful in the compositions of the present disclosure include, but are not limited to, wollastonite (calcium silicate) and titanium dioxide (TiO2). In certain embodiments, other additives may include infrared sunscreens, such as, but not limited to, titanium dioxide or silicon carbide, ceramicizing agents, such as, but not limited to, low-melting glass powder, calcium silicate or carbonizing agents, such as, but not limited to, phosphates and sulfates. In certain embodiments, additives may require special processing considerations, such as techniques to ensure that additives are evenly distributed and do not clump severely and cause product performance changes. Processing techniques may include other static and dynamic mixers, stabilizers, adjustment of process conditions, and other techniques known in the art. One or more fire additives may also be present in the final aerogel composition.

[0219] In certain embodiments, additives are included in the aerogel materials and compositions of the present disclosure, for example, aluminosilicate clay-based materials, such as halloysite or kaolin, which can provide improved high temperature shrinkage properties. An exemplary test method for high temperature shrinkage is "Standard Test Method for Linear Shrinkage of Prefabricated High Temperature Insulators Subjected to Uniform Heating" (ASTM C356, ASTM International, West Conshohocken, PA). In these tests, called "thermal soak", the material is exposed to a temperature above 1000°C for a duration of up to 60 minutes. In certain exemplary embodiments, the aerogel materials or compositions of the present disclosure may have a high temperature shrinkage of about 20% or less, about 15% or less, about 10% or less, about 6% or less, about 5% or less, 4% or less, 3% or less, 2% or less, 1% or less, or a combination of linear shrinkage, width shrinkage, thickness shrinkage, or shrinkage in any dimension within a range between any two of these values.

[0220] In some exemplary embodiments, certain base catalysts used to catalyze the precursor reaction can result in trace levels of alkali metals in the aerogel composition. Trace levels of alkali metals (e.g., sodium or potassium) in the aerogel material (e.g., 100 to 500 ppm) can have an adverse effect on high temperature shrinkage and thermal durability. However, without being bound by any particular mechanism or theory, aluminosilicate clay-based materials such as halloysite or kaolin can sequester fugitive alkali metals, such as sodium or potassium, thereby reducing or eliminating the effects of alkali metals on shrinkage and thermal durability. In certain embodiments of the present disclosure, the aluminosilicate clay material is in a dehydrated form, such as meta-halloysite or metakaolin. For example, an aerogel material or composition comprising metakaolin or meta-halloysite in an amount greater than about 0.5 wt% relative to the silica content can significantly reduce thermal shrinkage and thermal durability. In an exemplary embodiment, the aerogel material or composition can include an amount of metakaolin or meta-halloysite in the range of about 0.5 wt% to about 3.0 wt% relative to the silica content.

[0221] Figure 1 Test data of thermal control member or battery thermal management member material samples according to embodiments disclosed herein are shown, wherein a temperature of 650°C was applied to one surface of the thermal control member or battery thermal management member, i.e., the hot side, and the temperature of the other side of the thermal control member or battery thermal management member, i.e., the cold side, was measured over time. The control sample corresponds to the composition of Example 1, which will be described in more detail below. Samples A, B, and C are embodiments of thermal control members or battery thermal management members disclosed herein that include kaolin as an additive. Sample A corresponds to the composition of Example 2, which will be described in more detail below. Sample B corresponds to the composition of Example 4 below. Sample C corresponds to the composition of Example 3 below. As Figure 1 As shown, the composition including kaolin reached a temperature of 75° C. on the cold side in about 30 seconds, a temperature of 120° C. on the cold side in about 1 minute, a temperature of 150° C. on the cold side in about 90 seconds, and a temperature of 180° C. on the cold side in about 4 minutes. The unusually favorable performance of kaolin mineral as an additive in the temperature range below 200° C. is surprising and unexpected.

[0222] In certain embodiments of the present disclosure, a method for preparing an enhanced aerogel composition with fire-like performance is provided. The fire-like compositions of these embodiments also have hydrophobicity (as measured by moisture absorption and low thermal conductivity) sufficient to be used as an insulator in an industrial environment to help meet the growing energy-saving needs. To obtain these combinations of desired properties, simple loading additives or even fire-like additives will not succeed. Although multiple arrangements and combinations or multiple additives can be tried and optimized solutions are obtained, these efforts are not always successful, and there is a feasible production risk of repeatable quality control for these desired properties. The important aspect of these embodiments is to evaluate the thermal behavior of the composition (evaluated by thermogravimetric analysis or differential scanning calorimetry), otherwise the composition will provide all desired properties except fire resistance and consider the thermal decomposition starting temperature with the lower layer composition, or alternatively, the fire-like additive is a fire-like additive that matches the temperature of the maximum heat or the temperature of the maximum heat absorbed when the thermal decomposition starts.

[0223] In certain embodiments, the desired fire resistance of the final composition may include not only intrinsic properties, such as heat of combustion (ISO 1716), but also system flame properties, such as reaction to flame performance according to ISO 1182. In the case of ISO 1182, weight loss, furnace temperature rise, and flame time are evaluated when exposed to a furnace at a temperature of about 750°C.

[0224] The fiber or OCMF reinforced aerogel composition may have a variety of components that add oxidizable organic content (fuel) to the system. In addition, it may have a variety of other components that, although not fuel, may interfere with combustion when exposed to fire. Therefore, the combustion behavior of these systems cannot be predicted simply based on the constituent elements. Where multiple properties are desired, in certain embodiments, the composition should be obtained without regard to its fire properties, and the thermal properties of the resulting composition should be evaluated to find suitable fire additives that will provide fire properties without compromising other properties that the starting composition is intended to provide.

[0225] In certain embodiments, the onset of thermal decomposition is a key property of the composition. In certain other embodiments, for the purpose of developing enhanced fire resistant aerogel compositions, the peak exotherm temperature can be a key property. When multiple fuel components present in the composition are identified by multiple peaks in the DSC curve, these compositions will work well by matching the peak exotherm temperature of the enhanced aerogel composition with a fire-type additive having an endothermic peak exotherm temperature within 140°C, 120°C, 100°C or 80°C. In various embodiments, the endothermic peak exotherm temperature is within 50°C.

[0226] The aerogel materials and compositions of the present disclosure have been shown to be highly effective as thermal insulation materials. However, the application of the methods and materials of the present disclosure is not intended to be limited to applications related to thermal insulation. The methods and materials of the present disclosure can be applied to any system or application that would benefit from the unique combination of properties or procedures provided by the materials and methods of the present disclosure.

[0227] The following examples provide various non-limiting embodiments and properties of the present disclosure. In the following examples, the wt % of additives is referenced to the total weight of the aerogel composition as 100%. Figure 1 and Figure 2 is a diagram showing the thermal control means or battery thermal management means of the following embodiment controlling time and temperature behavior.

[0228] Example 1

[0229] A glass fiber reinforced silica aerogel composition was produced according to the method disclosed above. The reinforced silica aerogel composition has a thickness of about 3 mm and includes 21.7 wt % synthetic amorphous silica, 12.2 wt % methyl silylated silica, 62.27 wt % glass fibers and 3.8 wt % iron oxide (Fe2O3). Using the hot surface performance test, an 8-inch square sample of the composition was evaluated at 650°C with a hot surface. The temperature of the sample composition on the cold face was measured over a period of time. For the sample composition of this example, the time to reach a temperature of 75°C on the cold face was about 15 seconds, the time to reach a temperature of 120°C on the cold face was about 30 seconds, the time to reach a temperature of 150°C on the cold face was about 40 seconds and the time to reach a temperature of 180°C on the cold face was about 1 minute. The data for the sample composition of this example corresponds to Figure 1 ”Control” in the figure.

[0230] Example 2

[0231] A glass fiber reinforced silica aerogel composition was produced according to the method disclosed above. The reinforced silica aerogel composition has a thickness of about 3 mm and includes 15.3 wt% synthetic amorphous silica, 8.6 wt% methyl silylated silica, 37.8 wt% glass fibers and 38.3 wt% kaolin. The target silica density is 0.07 g / cc. Using the hot surface performance test, an 8-inch square sample of the composition was evaluated at 650°C with a hot surface. The temperature of the sample composition on the cold surface was measured over a period of time. For the sample composition of this example, the time to reach a temperature of 75°C on the cold surface was about 32 seconds, the time to reach a temperature of 120°C on the cold surface was about 1 minute, the time to reach a temperature of 150°C on the cold surface was about 90 seconds and the time to reach a temperature of 180°C on the cold surface was about 4 minutes. The data for the sample composition of this example corresponds to Figure 1 “A” in the figure.

[0232] Example 3

[0233] A glass fiber reinforced silica aerogel composition was produced according to the method disclosed above. The reinforced silica aerogel composition has a thickness of about 3 mm and includes 15.3 wt% synthetic amorphous silica, 8.6 wt% methyl silylated silica, 37.8 wt% glass fibers and 38.3 wt% kaolin. The target silica density is 0.09 g / cc. Using the hot surface performance test, an 8-inch square sample of the composition was evaluated at 650°C with a hot surface. The temperature of the sample composition on the cold side was measured over a period of time. For the sample composition of this example, the time to reach a temperature of 75°C on the cold side was about 38 seconds, the time to reach a temperature of 120°C on the cold side was about 68 seconds, the time to reach a temperature of 150°C on the cold side was about 102 seconds and the time to reach a temperature of 180°C on the cold side was about 4 minutes. The data for the sample composition of this example corresponds to Figure 1 “C” in the figure.

[0234] Example 4

[0235] A glass fiber reinforced silica aerogel composition was produced according to the method disclosed above. The reinforced silica aerogel composition has a thickness of about 3 mm and includes 15.3 wt% synthetic amorphous silica, 8.6 wt% methyl silylated silica, 37.8 wt% glass fibers and 38.3 wt% of a combination of kaolin and ATH. The density of the target silica is 0.07 g / cc. Using the hot surface performance test, an 8-inch square sample of the composition was evaluated at 650°C with a hot surface. The temperature of the sample composition on the cold side was measured over a period of time. For the sample composition of this example, the time to reach a temperature of 75°C on the cold side was about 36 seconds, the time to reach a temperature of 120°C on the cold side was about 1 minute, the time to reach a temperature of 150°C on the cold side was about 96 seconds and the time to reach a temperature of 180°C on the cold side was about 3 minutes and 21 seconds. The data for the sample composition of this example corresponds to Figure 1 “B” in the figure.

[0236] Example 5

[0237] A glass fiber reinforced silica aerogel composition was produced according to the method disclosed above. The reinforced silica aerogel composition has a thickness of about 3.5 mm and includes 21.7 wt % synthetic amorphous silica, 12.2 wt % methyl silylated silica, 62.27 wt % glass fibers and 3.8 wt % iron oxide (Fe2O3). Using the hot surface performance test, an 8-inch square sample of the composition was evaluated at 650°C with a hot surface. The temperature of the sample composition on the cold surface was measured over a period of time. For the sample composition of this example, the time to reach a temperature of 75°C on the cold surface was about 13 seconds, the time to reach a temperature of 120°C on the cold surface was about 22 seconds, the time to reach a temperature of 150°C on the cold surface was about 29 seconds and the time to reach a temperature of 180°C on the cold surface was about 36 seconds. The data for the sample composition of this example corresponds to Figure 2 ”Control” in the figure.

[0238] Example 6

[0239] Sols of both methyltriethoxysilane (MTES) and tetraethoxysilane (TEOS) or polyethyl silicate (Silbond 40) were prepared separately by hydrolysis in ethanol under acidic conditions. The proportions and concentrations of the sol materials were adjusted to obtain a hydrophobe content of about 36 wt % from MTES and an aerogel with an organic content of about 8.0 wt % in the aerogel material. Silicon carbide (SiC) was incorporated into the combined sol at a weight percentage of at least 35 wt % relative to the silicon dioxide content. The combined sol was then stirred for not less than 1 hour.

[0240] Guanidine hydroxide (2M) was added to the combined sol at a concentration sufficient to achieve a target aerogel density of about 0.07-0.085 g / cc. The catalytic sol containing SiC was poured into the fiber reinforcement phase and allowed to gel. The fiber-reinforced wet gel was subjected to a series of molding steps using heavy stainless steel rollers immediately before and after gelation. The wet gel was repeatedly rolled no more than 4 times using a rigid incompressible gauge block positioned at the edge of the wet gel and the thickness was controlled to 3.0 mm. After curing at room temperature for no more than 1 hour, the aerogel material was aged at 68°C in an ethanol aging solution with a fluid: gel ratio of about 3:1 for about 12 hours. The aged gel was solvent extracted with supercritical CO2 and then dried at 110°C for 2 hours.

[0241] The fiber reinforcement phase is a homogeneous nonwoven material composed of textile grade glass fibers (E-glass composition) which is about 5.6 mm thick and has a density of about 250 g / m 2 The resulting reinforced silica aerogel composition was about 2.5 mm thick and was about 44% aerogel (comprising about 28% synthetic amorphous silica and about 16% methyl silylated silica), 41% fiberglass, and 15% silicon carbide by weight of the reinforced silica aerogel composition, resulting in an expected material density of about 0.20 g / cc (assuming an aerogel density of 0.085 g / cc).

[0242] Using the Hot Surface Performance Test, an 8 inch square sample of the composition was evaluated with a hot surface at 650°C. The temperature of the sample composition on the cold side was measured over a period of time. For the sample composition of this example, the time to reach a temperature of 75°C on the cold side was about 13 seconds, the time to reach a temperature of 120°C on the cold side was about 24 seconds, the time to reach a temperature of 150°C on the cold side was about 31 seconds and the time to reach a temperature of 180°C on the cold side was about 42 seconds. The data for the sample composition of this example corresponds to Figure 2 “E” in the figure.

[0243] Example 7

[0244] Sols of both methyltriethoxysilane (MTES) and tetraethoxysilane (TEOS) or polyethyl silicate (Silbond 40) were prepared separately by hydrolysis in ethanol under acidic conditions. The proportions and concentrations of the sol materials were adjusted to obtain a hydrophobe content of about 36 wt % from MTES and an aerogel with an organic content of about 8.0 wt % in the aerogel material. Silicon carbide (SiC) was incorporated into the combined sol at a weight percentage of at least 35 wt % relative to the silicon dioxide content. The combined sol was then stirred for not less than 1 hour.

[0245] Guanidine hydroxide (2M) was added to the combined sol at a concentration sufficient to achieve a target aerogel density of about 0.07-0.085 g / cc. The catalytic sol containing SiC was poured into the fiber reinforcement phase and allowed to gel. The fiber reinforced wet gel was subjected to a series of molding steps using heavy stainless steel rollers immediately before and after gelation. The wet gel was repeatedly rolled no more than 4 times using a rigid incompressible gauge block positioned at the edge of the wet gel and the thickness was controlled to 2.0 mm. After curing at room temperature for no more than 1 hour, the aerogel material was aged at 68°C in an ethanol aging solution with a fluid: gel ratio of about 3:1 for about 12 hours. The aged gel was solvent extracted with supercritical CO2 and then dried at 110°C for 2 hours.

[0246] The fiber reinforcement phase is a homogeneous nonwoven material composed of textile grade glass fibers (E-glass composition) which is about 5.6 mm thick and has a density of about 250 g / m 2 The resulting reinforced silica aerogel composition was about 2.0 mm thick and was about 36% aerogel (comprising about 23% synthetic amorphous silica and about 13% methyl silylated silica), 51% fibers, and 13% silicon carbide by weight of the reinforced silica aerogel composition, resulting in an expected material density of about 0.20 g / cc (assuming an aerogel density of 0.085 g / cc).

[0247] Using the Hot Surface Performance Test, an 8 inch square sample of the composition was evaluated with a hot surface at 650°C. The temperature of the sample composition on the cold side was measured over a period of time. For the sample composition of this example, the time to reach a temperature of 75°C on the cold side was about 11 seconds, the time to reach a temperature of 120°C on the cold side was about 21 seconds, the time to reach a temperature of 150°C on the cold side was about 31 seconds and the time to reach a temperature of 180°C on the cold side was about 39 seconds. The data for the sample composition of this example corresponds to Figure 2 “D” in the figure.

[0248] Samples of the composition were evaluated in compression. The sample deformation was measured to provide a stress-strain relationship for the sample. Figure 3 Data from this analysis are shown.

[0249] Example 8

[0250] Sols of both methyltriethoxysilane (MTES) and tetraethoxysilane (TEOS) or polyethyl silicate (Silbond 40) were prepared separately by hydrolysis in ethanol under acidic conditions. The proportions and concentrations of the sol materials were adjusted to obtain a hydrophobe content of about 36 wt % from MTES and an aerogel with an organic content of about 8.0 wt % in the aerogel material. Silicon carbide (SiC) was incorporated into the combined sol at a weight percentage of at least about 10 wt % relative to the silicon dioxide content. The combined sol was then stirred for not less than 1 hour.

[0251] Guanidine hydroxide (2M) was added to the combined sol at a concentration sufficient to achieve a target aerogel density of about 0.07-0.085 g / cc. The catalytic sol containing SiC was poured into the fiber reinforcement phase and allowed to gel. The fiber reinforced wet gel was subjected to a series of molding steps using heavy stainless steel rollers immediately before and after gelation. The wet gel was repeatedly rolled no more than 4 times using a rigid incompressible gauge block positioned at the edge of the wet gel and the thickness was controlled to be 3.0 mm. After curing at room temperature for no more than 1 hour, the aerogel material was aged at 68°C in an ethanol aging solution with a fluid:gel ratio of about 3:1 for about 12 hours. The aged gel was solvent extracted with supercritical CO2 and then dried at 110°C for 2 hours.

[0252] The fiber reinforcement phase is a homogeneous nonwoven material consisting of textile grade glass fibers (E-glass composition) which is about 4 mm thick and has a density of about 225 g / m 2 The resulting reinforced silica aerogel composition was about 2.25 mm thick and was about 39% aerogel (comprising about 25% synthetic amorphous silica and about 14% methyl silylated silica), 57% fiberglass, and 4% silicon carbide by weight of the reinforced silica aerogel composition, resulting in an expected material density of about 0.16 g / cc (assuming an aerogel density of 0.075 g / cc).

[0253] Using the Hot Surface Performance Test, an 8 inch square sample of the composition was evaluated with a hot surface at 650°C. The temperature of the sample composition on the cold side was measured over a period of time. For the sample composition of this example, the time to reach a temperature of 75°C on the cold side was about 9 seconds, the time to reach a temperature of 120°C on the cold side was about 19 seconds, the time to reach a temperature of 150°C on the cold side was about 25 seconds and the time to reach a temperature of 180°C on the cold side was about 34 seconds. Figure 4 The data for the sample compositions of this example are shown in the graphs.

[0254] The above advantages as well as those apparent from the above description are effectively obtained.Since certain changes may be made in the above construction without departing from the scope of the invention, it is intended that all matter contained in the above description or shown in the accompanying drawings shall be interpreted as illustrative in an illustrative sense and not in a limiting sense.

[0255] It is also to be understood that the appended claims are intended to cover all generic and specific features of the invention described herein, and all statements which, as a matter of language, are intended to indicate the scope of the invention are to fall therebetween.

Claims

1. A battery thermal management component, comprising: A heat shield comprising an aerogel composition, wherein the heat shield has a thermal conductivity of less than 65 mW / mK; and Wherein, the battery thermal management component shows a compressibility of less than 70% at 345 kPa.

2. A battery thermal management component, comprising: A heat shield comprising an aerogel composition, wherein the heat shield has a thermal conductivity of less than 65 mW / mK; and Wherein, the battery thermal management component exhibits a compressive force deflection of 5 kPa to 500 kPa at 25% deflection.

3. The battery thermal management component according to claim 1 or claim 2, further comprising: an elastic layer comprising an organic material, the elastic layer contacting the aerogel composition; and The aerogel composition maintains at least one surface of the elastic layer at a temperature lower than the decomposition temperature of the organic material.

4. The battery thermal management component according to claim 1 or claim 2, wherein: The heat protection layer also includes mica material.

5. The battery thermal management component according to claim 1 or claim 2, wherein: The heat protection layer also includes microporous silica, ceramic fiber, mineral wool or a combination thereof.

6. The battery thermal management component according to claim 1, wherein: The battery thermal management component exhibits a compressibility of less than 25% at 25 kPa.

7. The battery thermal management component according to claim 1, wherein: The battery thermal management component exhibits a compressibility of less than 25% within a range of 25 kPa to 35 kPa.

8. The battery thermal management component according to claim 1, wherein: The battery thermal management component exhibits a compressibility of less than 50% at 50 kPa.

9. The battery thermal management component according to claim 1, wherein: The battery thermal management component exhibits a compressibility of less than 80% at 245 kPa.

10. The battery thermal management component according to claim 1, wherein: The battery thermal management component exhibits a compressibility of less than 70% at 235 kPa.

11. The battery thermal management component according to claim 2, wherein: The battery thermal management component exhibits a compressive force deflection of 5 kPa to 80 kPa at 25% deflection.

12. The battery thermal management component according to claim 1 or claim 2, wherein: The battery thermal management component has sufficient elasticity to return to at least 80%, 75%, 65%, 60% or 50% of its original thickness.

13. The battery thermal management component according to claim 1 or claim 2, wherein: The thermal conductivity of the battery thermal management component is maintained under compression at less than 60 mW / mK, 50 mW / mK, 40 mW / mK, 30 mW / mK, 25 mW / mK, or a range between any of these values.

14. The battery thermal management component according to claim 1 or claim 2, in, The heat protection layer is a first heat protection layer, Wherein, the battery thermal management component further comprises a second heat protection layer and at least one elastic layer, and Wherein, at least one of the first heat protection layer and the second heat protection layer is arranged to contact the at least one elastic layer.

15. The battery thermal management component according to claim 1 or claim 2, wherein: The battery thermal management component includes a multi-layer aerogel composition or a reinforced aerogel composition.

16. The battery thermal management component according to claim 1 or claim 2, wherein: The aerogel composition has an uncompressed thickness of 1 mm to 10 mm.

17. The battery thermal management component according to claim 1 or claim 2, wherein: The heat protection layer is surrounded by a packaging member.

18. A battery thermal management component, comprising: Thermal protection layer; as well as at least one elastic layer comprising one or more organic materials; wherein the heat protection layer is arranged to contact the elastic layer, wherein the heat protection layer has a thermal conductivity of less than 65 mW / mK, and The heat protection layer maintains at least one surface of the elastic layer at a temperature lower than a decomposition temperature of at least one of the organic materials.

19. The battery thermal management component according to claim 18, wherein: The heat protection layer comprises a material selected from the group consisting of mica, mica board, microporous silica, ceramic fiber, mineral wool, inorganic ceramic paper and combinations thereof.

Citation Information

Patent Citations

  • Ormosil aerogels containing silicon bonded linear polymers

    US20050192367A1

  • Flexible coherent insulating structures

    US20070173157A1

  • Open-Cell Foam Materials, Method For Producing Them And Their Use

    US20070213417A1

  • Melamine resin foams with nanoporous fillers

    US20120142802A1

  • Hydrophobic aerogel materials

    US20160096949A1